Fe-based amorphous alloy thin strip and manufacturing method thereof, iron core and transformer
By employing CW oscillation to form linear laser marks on Fe-based amorphous alloy strips with specific parameters, the method addresses productivity and deformation issues, achieving reduced iron loss and improved magnetic properties for transformers.
Patent Information
- Application Number
- CN202080040217.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-03-25
- Filing Date
- 2020-06-24
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2040-06-24
AI Technical Summary
Existing methods for reducing iron loss in Fe-based amorphous alloy thin strips, particularly under higher magnetic flux densities, face challenges in productivity and deformation, and fail to achieve minimum iron loss values required for efficient transformers.
The method involves forming continuous linear laser irradiation marks on the Fe-based amorphous alloy strips using a CW (continuous wave) oscillation mode, with specific height and width parameters, and arranging these marks perpendicular to the casting direction to minimize deformation and enhance magnetic properties.
This approach results in Fe-based amorphous alloy strips with reduced iron loss, lower deformation, and improved productivity, suitable for transformers with enhanced performance under higher magnetic flux densities.
Smart Images

Figure CN113892154B_ABST
Abstract
Description
[0001] Cross-reference to related applications
[0002] This international application claims the priority based on Japanese Patent Application No. 2019-121525 filed in the Japan Patent Office on June 28, 2019, the priority based on Japanese Patent Application No. 2020-024119 filed in the Japan Patent Office on February 17, 2020, the priority based on Japanese Patent Application No. 2020-054544 filed in the Japan Patent Office on March 25, 2020, and the priority based on Japanese Patent Application No. 2019-178568 filed in the Japan Patent Office on September 30, 2019, and the entire contents of Japanese Patent Application No. 2019-121525, Japanese Patent Application No. 2020-024119, Japanese Patent Application No. 2020-054544 and Japanese Patent Application No. 2019-178568 are incorporated herein by reference. Technical Field
[0003] The invention relates to a Fe-based amorphous alloy thin strip and a manufacturing method thereof, an iron core and a transformer. Background Art
[0004] Fe-based amorphous (non-crystalline) alloy thin strips are becoming increasingly popular as, for example, core materials for transformers.
[0005] As methods for reducing abnormal eddy current loss of Fe-based amorphous alloy thin strips, known methods include mechanically scraping the surface of the Fe-based amorphous alloy thin strips, irradiating the surface of the Fe-based amorphous alloy thin strips with laser to locally melt them, and rapidly solidifying them to subdivide the magnetic domains with laser scribing.
[0006] As a laser scribing method, for example, Japanese Patent Gazette No. 3-32886 discloses a method of subdividing the magnetic domains by irradiating amorphous alloy thin strips with pulsed laser in the width direction to locally and instantly melt the surface of the amorphous alloy thin strips, and then rapidly cooling and solidifying the strips to form amorphous spots in the form of point arrays.
[0007] Japanese Patent Application Laid-Open No. 61-258404 discloses irradiating a thin ribbon with laser light while scanning the thin ribbon in the width direction while the surface temperature of the thin ribbon is 300° C. or higher.
[0008] Japanese Patent Gazette No. 2-53935 discloses that by locally heating a thin strip, strip-shaped crystallized regions are formed in the long side direction of the thin strip at intervals of 2 to 100 mm and at an angle θ of less than 30° with the width direction of the thin strip, and at the same time, the ratio d / D of the average depth d of each region in the thickness direction of the plate to the thickness D of the thin strip is made greater than 0.1, and the proportion of these regions in the thin strip is made less than 8 volume %.
[0009] In addition, transformers have a variety of structures from small to large, and are used in all aspects of the living environment. In addition, due to their large usage, they have become a major factor in power loss, and there has always been a demand to suppress the loss in transformers. Therefore, countries around the world have established standards for suppressing their losses. Representative standards include Japan's Top Runner standards JIS C 4304: 2013 and JIS C 4306: 2013, the US DOE standard US Department of Energy 10 CFR Part 431.196, the EU standard Commotions Regulation (EU) No. 548 / 2014, the Chinese national standard GB 20052-2013, the Indian standard IS 1180 (Part 1): 2018, etc., and the allowable loss or energy efficiency is tightened every time the regular revision work is carried out. For this reason, as a way to cope with these standards, high-efficiency transformers with less loss are gradually becoming popular.
[0010] Transformers are mainly composed of an iron core and a winding. As the iron core, a grain-oriented electromagnetic steel sheet is generally used. However, Fe-based amorphous alloy strips are also available as a material with lower loss than grain-oriented electromagnetic steel sheets, and iron cores using these Fe-based amorphous alloy strips are also used.
[0011] The losses of transformers can be roughly divided into no-load losses (iron losses) that are generated by the core and are always generated regardless of the load current, and load losses (copper losses) that are generated by the winding and are proportional to the square of the load current. Although research on reducing each loss has been repeatedly conducted and improvements in losses have been seen, there is still a demand for further reductions in losses.
[0012] In order to reduce the no-load losses of transformers, some methods have been proposed.
[0013] In Japanese Patent Gazette No. 2017-54896, in order to obtain an efficient iron core with reduced no-load loss, a wound iron core using amorphous material is adopted in which the joint structure on the inner circumference is set to overlapping joint, the joint structure on the outer circumference is set to step joint, and the proportion of the iron core with the overlapping structure arranged on the inner circumference is set to 32 to 62%.
[0014] Japanese Patent Gazette No. 2008-71982 provides a transformer comprising an iron core formed by molding amorphous alloy strips into multi-layer rings and an excitation winding, wherein an insulating film is formed on the surface of the amorphous alloy strips forming the iron core. By forming the insulating film on the surface of the amorphous alloy strips, the increase of eddy current loss can be suppressed and the no-load loss of the transformer can be reduced.
[0015] Japanese Patent Publication No. 2005-72160 provides a three-phase five-column wound core transformer, which is a structure in which both amorphous alloy thin strips and electromagnetic steel sheets are used as magnetic materials for the wound core. Specifically, in the three-phase five-column wound core transformer, the wound core that is linked to only one outer winding is set as an electromagnetic steel sheet, and the central wound core that is linked to two windings is set as an amorphous alloy thin strip. As a result, there is no need to press the reinforcing material of the winding, making the structure compact, thereby achieving the purpose of providing an amorphous alloy thin strip wound core and a three-phase five-column wound core transformer that reduces the man-hours and material costs of assembly work and further reduces the no-load loss compared to when the magnetic material is only the electromagnetic steel sheet.
[0016] Prior art literature
[0017] Patent Literature
[0018] Patent Document 1: Japanese Patent Publication No. 3-32886
[0019] Patent Document 2: Japanese Patent Application Laid-Open No. 61-258404
[0020] Patent Document 3: Japanese Patent Publication No. 2-53935
[0021] Patent Document 4: Japanese Patent Application Publication No. 2017-54896
[0022] Patent Document 5: Japanese Patent Application Publication No. 2008-71982
[0023] Patent Document 6: Japanese Patent Application Publication No. 2005-72160 Summary of the invention
[0024] Problems to be solved by the invention
[0025] Conventionally, when measuring the iron loss of Fe-based amorphous alloy thin strips, the measurement is generally performed under the condition of a magnetic flux density of 1.3 T (see, for example, the embodiments of Japanese Patent Publication No. 3-32886, Japanese Patent Application Laid-Open No. 61-258404, and Japanese Patent Publication No. 2-53935).
[0026] However, in recent years, from the viewpoint of miniaturization of transformers made of Fe-based amorphous alloy thin strips, it is sometimes required to reduce the iron loss under the condition of magnetic flux density of 1.45T instead of the iron loss under the condition of magnetic flux density of 1.3T.
[0027] In addition, the conventional laser irradiation method uses pulsed laser to form dot-shaped irradiation marks. The method using pulsed laser has problems in productivity and cost increase.
[0028] In addition, there is a case where the surface morphology of the amorphous alloy ribbon is greatly deformed due to laser irradiation. In the case of large deformation, the occupancy rate of the amorphous alloy ribbon when the amorphous alloy ribbon is wound or stacked to form a magnetic core becomes low. Such a large deformation of the surface morphology of the amorphous alloy ribbon is not a satisfactory form for the magnetic core properties. In addition, if a crystallized region is formed by locally heating the ribbon, the desired properties cannot be obtained due to crystallization.
[0029] In addition, as mentioned above, the no-load loss caused by the core and the load loss caused by the winding constitute the main losses of the transformer. In order to reduce the no-load loss of the transformer, it is considered to use Fe-based amorphous alloy thin strips with small iron loss. In particular, in the case of distribution transformers, as described in Takagi, Yamamoto, and Yamaji: "Evaluation of amorphous transformers using a model of pole-mounted transformer load mode" P885-892, Electric Theory B, Vol. 128, No. 6, 2008, or Final Report, LOT 2: Distribution and power transformers Tasks 1-7 2010 / ETE / R / 106, January 2011, the average equivalent load factor equivalent to the effective value of the load factor throughout the year is as low as about 15%, and the transformer using Fe-based amorphous alloy thin strips with small no-load loss is extremely effective from the perspective of energy saving and reduction of CO2 emissions.
[0030] As the iron core of the transformer, Fe-based amorphous alloy strips are roughly divided into two types, ordinary materials and high magnetic flux density materials, as recorded in Table 1 and Table 2 of JIS C 2534: 2017 (corresponding to IEC standard IEC60404-8-11), and there are 16 types of each based on the maximum value of iron loss and the minimum value of occupancy rate. As the material with the smallest iron loss, the maximum value of iron loss at a frequency of 50 Hz and a magnetic flux density of 1.3 T is 0.08 W / kg, and the maximum value of iron loss at a frequency of 60 Hz and a magnetic flux density of 1.3 T is 0.11 W / kg. However, in order to obtain a more efficient transformer, it is necessary to use Fe-based amorphous alloy strips with smaller iron loss for the iron core.
[0031] In order to reduce the iron loss of amorphous alloy thin strips, the aforementioned laser scribing method was attempted, but the iron loss did not reach the minimum iron loss values recorded in Tables 1 and 2 of the above-mentioned JIS C 2534:2017 (see, for example, the embodiments of Japanese Patent Gazette No. 3-32886, Japanese Patent Publication No. 61-258404, and Japanese Patent Gazette No. 2-53935).
[0032] Therefore, one embodiment of the present disclosure preferably provides an Fe-based amorphous alloy ribbon that can reduce iron loss under a magnetic flux density of 1.45 T. In addition, it is preferable to provide a production method that can obtain a Fe-based amorphous alloy ribbon with required properties and little deformation and has high productivity.
[0033] Another aspect of the present disclosure preferably provides an iron core and a transformer having excellent performance using the Fe-based amorphous alloy thin strip of the above aspect.
[0034] Methods for solving problems
[0035] One embodiment of the present disclosure is an Fe-based amorphous alloy strip having a first surface and a second surface. The Fe-based amorphous alloy strip has a plurality of continuous linear laser irradiation marks on at least the first surface. The linear laser irradiation marks are arranged in a direction perpendicular to the casting direction of the Fe-based amorphous alloy strip. The surface of the linear laser irradiation marks has irregularities, and when the irregularities are evaluated in the casting direction, the height difference HL calculated from the height difference HL between the highest point and the lowest point in the thickness direction of the Fe-based amorphous alloy strip and the length of the linear laser irradiation marks in the first surface in the casting direction, i.e., the width WA, is 6.0 to 180 μm. 2 .
[0036] In one embodiment of the present disclosure, the line width WA may be 28 μm or more.
[0037] In one aspect of the present disclosure, the height difference HL may be 0.20 μm or more.
[0038] In one embodiment of the present disclosure, the linear laser irradiation mark is a molten solidified portion that is melted and solidified by irradiating the first surface with laser, and can reach the second surface from the first surface. The width ratio WB / WA of the length in the casting direction of the linear laser irradiation mark on the second surface, i.e., the width WB to the width WA, can be 0.57 or less.
[0039] Another embodiment of the present disclosure is an Fe-based amorphous alloy strip having a first surface and a second surface. The Fe-based amorphous alloy strip has a plurality of continuous linear laser irradiation marks at least on the first surface. The linear laser irradiation marks are arranged in a direction orthogonal to the casting direction of the Fe-based amorphous alloy strip. The linear laser irradiation marks are molten solidified portions that are melted and solidified by irradiating the first surface with laser light, and extend from the first surface to the second surface. The width ratio WB / WA of the length in the casting direction of the linear laser irradiation marks on the second surface, i.e., the width WB, to the length in the casting direction of the linear laser irradiation marks on the first surface, i.e., the width WA, is less than 0.57.
[0040] In one embodiment of the present disclosure, the surface of the linear laser irradiation mark has unevenness. When the unevenness is evaluated in the casting direction, the height difference HL×width WA calculated from the height difference HL between the highest point and the lowest point in the thickness direction of the Fe-based amorphous alloy thin strip and the width WA can be 6.0 to 180 μm. 2 .
[0041] In one aspect of the present disclosure, the height difference HL may be 0.20 μm or more.
[0042] Another embodiment of the present disclosure is an Fe-based amorphous alloy thin strip having a first surface and a second surface. The Fe-based amorphous alloy thin strip has a plurality of continuous linear laser irradiation marks at least on the first surface. The linear laser irradiation marks are arranged in a direction orthogonal to the casting direction of the Fe-based amorphous alloy thin strip. The length of the linear laser irradiation marks in the casting direction on the first surface, i.e., the width WA, is greater than 28.5 μm and less than 90 μm.
[0043] In one aspect of the present disclosure, when the interval between mutually adjacent linear laser irradiation marks among a plurality of linear laser irradiation marks is defined as a line interval, the line interval may be 2 mm to 200 mm.
[0044] In one aspect of the present disclosure, the portion where the linear laser irradiation mark is provided may be amorphous.
[0045] In one method of the present disclosure, when the direction orthogonal to the casting direction is set as the width direction, in the width direction, the proportion of the length of the linear laser irradiation mark in the total length of the Fe-based amorphous alloy strip can be in the range of 10% to 50% in the directions from the center of the width direction of the Fe-based amorphous alloy strip toward the two ends in the width direction.
[0046] One aspect of the present disclosure may include a free solidification surface and a roller surface as the first surface and the second surface. The maximum cross-sectional height Rt of a portion other than the linear laser irradiation mark of the free solidification surface may be 3.0 μm or less.
[0047] In one aspect of the present disclosure, the thickness may be 18 μm to 35 μm.
[0048] In one embodiment of the present invention, the alloy composition of the Fe-based amorphous alloy strip consists of Fe, Si, B and impurities. When the total content of Fe, Si and B is set to 100 atomic %, the Fe content can be greater than 78 atomic %, the B content can be greater than 10 atomic %, and the total content of B and Si can be 17 atomic % to 22 atomic %.
[0049] In one embodiment of the present disclosure, the iron loss under the conditions of a frequency of 60 Hz and a magnetic flux density of 1.45 T may be 0.150 W / kg or less.
[0050] In one embodiment of the present disclosure, the iron loss under the conditions of a frequency of 1 kHz and a magnetic flux density of 1 T can be 8.6 W / kg or less, and the excitation power VA can be 8.7 VA / kg or less.
[0051] In one embodiment of the present disclosure, the coercive force Hc of the DC BH curve measured at a maximum applied magnetic field of 800 A / m may be 5.0 A / m or less.
[0052] In one aspect of the present disclosure, the squareness ratio [residual magnetic flux density Br / maximum magnetic flux density Bm] of the DC BH curve measured at a maximum applied magnetic field of 800 A / m may be 40% or less.
[0053] Another method of the present disclosure is a method for manufacturing an Fe-based amorphous alloy ribbon, wherein at least the first surface of the Fe-based amorphous alloy ribbon having a first surface and a second surface is irradiated with a laser using a CW (continuous wave) oscillation mode, thereby obtaining an Fe-based amorphous alloy ribbon having a plurality of linear laser irradiation marks. The laser density of the CW (continuous wave) oscillation mode laser is 5 J / m or more and 35 J / m or less. The linear laser irradiation marks are arranged in a direction orthogonal to the casting direction of the Fe-based amorphous alloy ribbon.
[0054] In one embodiment of the present disclosure, the surface of the linear laser irradiation mark has unevenness, and when the unevenness is evaluated in the casting direction, the height difference HL×width WA calculated from the height difference HL between the highest point and the lowest point in the thickness direction of the Fe-based amorphous alloy thin strip and the length of the linear laser irradiation mark in the casting direction on the first surface, that is, the width WA, can be 6.0 to 180 μm. 2 .
[0055] In one embodiment of the present disclosure, the linear laser irradiation mark may extend from the first surface to the second surface. The width ratio WB / WA of the length in the casting direction of the linear laser irradiation mark on the second surface, i.e., the width WB, to the length in the casting direction of the linear laser irradiation mark on the first surface, i.e., the width WA, may be 0.57 or less.
[0056] In one aspect of the present disclosure, the length of the linear laser irradiation mark in the first surface in the casting direction, that is, the width WA may be 28 μm or more.
[0057] In one embodiment of the present disclosure, the surface of the linear laser irradiation mark has irregularities, and when the irregularities are evaluated in the casting direction, the height difference HL between the highest point and the lowest point in the thickness direction of the Fe-based amorphous alloy ribbon may be 0.20 to 2.0 μm.
[0058] In one aspect of the present disclosure, the portion where the linear laser irradiation mark is provided may be amorphous.
[0059] In one aspect of the present disclosure, when the interval between mutually adjacent linear laser irradiation marks among a plurality of linear laser irradiation marks is defined as a line interval, the line interval may be 2 mm to 200 mm.
[0060] Another aspect of the present disclosure is an iron core formed by laminating a plurality of the above-mentioned Fe-based amorphous alloy thin strips, or by winding at least one of the above-mentioned Fe-based amorphous alloy thin strips.
[0061] In one embodiment of the present disclosure, a plurality of Fe-based amorphous alloy ribbons stacked together may be bent and wound to form a structure. The iron loss under the conditions of a frequency of 60 Hz and a magnetic flux density of 1.45 T may be 0.240 W / kg or less.
[0062] Another aspect of the present disclosure is a transformer including an iron core using the Fe-based amorphous alloy thin strip and a coil wound around the iron core.
[0063] In one embodiment of the present disclosure, the iron core is formed by bending and winding a plurality of stacked Fe-based amorphous alloy thin strips, and the iron loss under the conditions of a frequency of 60 Hz and a magnetic flux density of 1.45 T can be 0.240 W / kg or less.
[0064] One embodiment of the present disclosure is a single-phase transformer, in which the no-load loss per unit weight of the core at 50 Hz can be less than 0.15 W / kg, or the no-load loss per unit weight of the core at 60 Hz can be less than 0.19 W / kg.
[0065] One embodiment of the present disclosure is a three-phase transformer, in which the no-load loss per unit weight of the core at 50 Hz can be 0.19 W / kg or less, or the no-load loss per unit weight of the core at 60 Hz can be 0.24 W / kg or less.
[0066] In one aspect of the present disclosure, the rated capacity may be 10 kVA or more.
[0067] Effects of the Invention
[0068] According to one embodiment of the present disclosure, a Fe-based amorphous alloy thin strip with low iron loss is provided. In addition, according to one embodiment of the present disclosure, a Fe-based amorphous alloy thin strip having required properties, low deformation degree caused by laser irradiation, and high productivity and a method for producing the same are provided.
[0069] According to another aspect of the present disclosure, there is provided an iron core and a transformer having excellent performance by using the Fe-based amorphous alloy thin strip of the above aspect. BRIEF DESCRIPTION OF THE DRAWINGS
[0070] [ Figure 1 ] is a schematic top view schematically showing the free solidification surface of the Fe-based amorphous alloy thin strip sheet (thin strip 10) after laser processing.
[0071] [ Figure 2 ] is a microscope photograph of linear laser irradiation marks.
[0072] [ Figure 3 ] is a schematic diagram of the uneven state of the surface of the linear laser irradiation mark.
[0073] [ Figure 4 ] is a graph showing the relationship between the height difference HL×width WA and the iron loss CL (60 Hz, 1.45 T).
[0074] [ Figure 5 ] is a graph showing the relationship between the width WA and the iron loss CL (60 Hz, 1.45 T).
[0075] [ Figure 6 ] is a graph showing the relationship between the height difference HL×width WA and the excitation power VA (60 Hz, 1.45 T).
[0076] [ Figure 7 ] is a graph showing the relationship between the height difference HL×width WA and the coercive force Hc (60 Hz, 1.45 T).
[0077] [ Figure 8 ] is a top view showing an example of an iron core.
[0078] [ Fig. 9 ] is a side view showing an example of an iron core.
[0079] [ Fig.10 ] is a circuit diagram showing a circuit for performing voltage transformation by winding a primary winding (N1) and a secondary winding (N2) around an iron core.
[0080] [ Fig.11 ] is a graph showing the relationship between the magnetic flux density and iron loss at a frequency of 50 Hz for the iron core of Example 3 and the iron core of Comparative Example 2.
[0081] [ Fig.12] is a graph showing the relationship between the magnetic flux density and the iron loss at a frequency of 60 Hz for the iron core of Example 3 and the iron core of Comparative Example 2.
[0082] [ Fig.13 ] is a microscope photograph of the linear laser irradiation mark on the laser-irradiated surface A of No.54.
[0083] [ Fig.14 ] is a microscope photograph of the linear laser irradiation marks on the back side B of the laser irradiated surface A of No.54.
[0084] [ Fig.15 ] is a microscope photograph of the linear laser irradiation mark on the laser irradiated surface A of No.*44.
[0085] [ Fig.16 ] is a microscope photograph of the linear laser irradiation marks on the back surface B of the laser irradiated surface A of No.*44.
[0086] [ Fig.17 ] Fig.17 A is a microscope photograph of the linear laser irradiation mark of No. 13 in Example 1, Fig.17 B is a microscopic photograph of the linear laser irradiation mark of No. 17 in Example 1, Fig.17 C is a microscopic photograph of the linear laser irradiation mark of No. 20 in Example 1, Fig.17 D is a microscopic photograph of the linear laser irradiation mark of No. 24 in Example 1.
[0087] [ Fig.18 ] Fig.18 A is a microscope photograph of the linear laser irradiation mark of No. 26 in Example 1, Fig.18 B is a microscopic photograph of the linear laser irradiation mark of No. 28 in Example 1. Fig.18 C is a microscopic photograph of the linear laser irradiation mark of No. 34 in Example 1, Fig.18 D is a microscopic photograph of the linear laser irradiation mark of No. 36 in Example 1.
[0088] [ Fig.19 ] is a graph showing the relationship between the width WA and the excitation power VA (60 Hz, 1.45 T).
[0089] [ Fig. 20 ] is a graph showing the relationship between the width WA and the coercive force Hc (60 Hz, 1.45 T).
[0090] [ Fig.21 ] is a graph showing the relationship between the line spacing LP1 and the iron loss CL (60 Hz, 1.45 T).
[0091] [ Fig. 22] is a graph showing the relationship between the width ratio WB / WA and the iron loss CL (60 Hz, 1.45 T).
[0092] [ Fig.23 ] is a graph showing the relationship between the height difference HL and the iron loss CL (1kHz, 1T).
[0093] [ Fig.24 ] is a graph showing the relationship between the high-low difference HL and the excitation power VA (1kHz, 1T).
[0094] [ Fig.25 ] is a graph showing the relationship between the height difference HL×width WA and the iron loss CL (1 kHz, 1 T).
[0095] [ Fig.26 ] is a graph showing the relationship between the level difference HL×width WA and the excitation power VA (1kHz, 1T).
[0096] [ Fig. 27 ] is a graph showing the relationship between laser density and iron loss CL (1kHz, 1T).
[0097] [ Fig.28 ] is a graph showing the relationship between laser density and excitation power VA (1kHz, 1T).
[0098] [ Fig.29 ] is a graph showing the relationship between laser density and iron loss CL (60 Hz, 1.45 T).
[0099] [ Fig.30 ] is a graph showing the relationship between laser density and excitation power VA (60 Hz, 1.45 T).
[0100] [ Fig.31 ] is a graph showing the relationship between laser density and coercive force Hc (60 Hz, 1.45 T).
[0101] [ Fig.32 ] is a microscope photograph of the linear laser irradiation mark of Example 2.
[0102] [ Fig.33 ] is a schematic diagram showing an example of a transformer according to the present embodiment.
[0103] [ Fig.34 ] is a schematic diagram showing another example of the transformer of the present embodiment.
[0104] [ Fig.35 ] is a schematic diagram showing another example of the transformer of the present embodiment. DETAILED DESCRIPTION
[0105] In this specification, the meaning of the numerical range represented by "~" is a range that includes the numerical values recorded before and after "~" as the lower limit and upper limit. In this specification, in the numerical range recorded in stages, the upper limit or lower limit recorded in one numerical range can be replaced by the upper limit or lower limit of the numerical range recorded in other stages. In addition, in the numerical range recorded in this specification, the upper limit or lower limit of its numerical range can be replaced by the value shown in the embodiment.
[0106] In the present specification, the term "step" includes not only an independent step but also a step that cannot be clearly distinguished from other steps as long as the intended purpose of the step can be achieved.
[0107] In this specification, the Fe-based amorphous alloy thin strip refers to a thin strip composed of a Fe-based amorphous alloy.
[0108] In this specification, the Fe-based amorphous alloy refers to an amorphous alloy containing Fe (iron) as a main component. Here, the main component refers to a component with the highest content ratio (mass %).
[0109] Hereinafter, embodiments of the present disclosure will be described. It should be noted that the present disclosure is not limited to the embodiments described below, and can be appropriately modified within the scope of the technical concept.
[0110] The Fe-based amorphous alloy thin strip disclosed in the present invention is an Fe-based amorphous alloy thin strip in which strain is introduced into the alloy thin strip by laser irradiation, thereby subdividing the magnetic domains and improving the magnetic properties.
[0111] In the present disclosure, a linear laser irradiation mark is formed by irradiating a Fe-based amorphous alloy thin strip with a laser using a CW (continuous wave) oscillation mode. The linear laser irradiation mark is a molten solidified portion that is melted and solidified due to laser irradiation, and can be formed into a continuous linear shape by irradiating a laser using a CW (continuous wave) oscillation mode.
[0112] In the present disclosure, the magnetic properties are improved by performing the above-mentioned laser irradiation, but the target magnetic properties cannot be obtained if the energy of the laser irradiation is too strong or too weak. Therefore, in the present disclosure, a suitable linear laser irradiation mark is formed by suitable laser irradiation, and a suitable linear laser irradiation mark shape is provided.
[0113] 〔Fe-based amorphous alloy ribbon〕
[0114] The Fe-based amorphous alloy strip of the first embodiment of the present disclosure has a first surface and a second surface. The Fe-based amorphous alloy strip has a plurality of continuous linear laser irradiation marks on at least the first surface. The linear laser irradiation marks are arranged in a direction perpendicular to the casting direction of the Fe-based amorphous alloy strip. The surface of the linear laser irradiation marks has irregularities. When the irregularities are evaluated in the casting direction, the height difference HL calculated from the height difference HL between the highest point and the lowest point in the thickness direction of the Fe-based amorphous alloy strip and the length of the linear laser irradiation marks in the first surface in the casting direction, i.e., the width WA, is 6.0 to 180 μm. 2 .
[0115] The height difference HL×width WA is 6.0 to 180 μm 2 , thereby achieving the target magnetic properties. For example, a Fe-based amorphous alloy thin strip having an iron loss of 0.150 W / kg or less under the conditions of a frequency of 60 Hz and a magnetic flux density of 1.45 T can be obtained.
[0116] The height difference HL×width WA is preferably 178 μm 2 Below, more preferably 175 μm 2 In addition, the height difference HL×width WA is preferably 6.4 μm. 2 More preferably, 10 μm 2 above.
[0117] In the embodiment of the present disclosure, the width WA is preferably 28 μm or more. Further, the width WA is preferably 28.5 μm or more, more preferably 29 μm or more, and further preferably 30 μm or more.
[0118] In addition, in the embodiment of the present disclosure, the height difference HL is preferably 0.20 μm or more. Further, the height difference HL is preferably 0.21 μm or more, more preferably 0.24 μm or more, more preferably 0.25 μm or more, and more preferably 0.30 μm or more. In addition, the height difference HL is preferably 2.0 μm or less. Further preferably, it is less than 2.0 μm, further preferably 1.9 μm or less, further preferably 1.8 μm or less, and further preferably 1.7 μm or less.
[0119] In addition, in the embodiment of the present disclosure, the width ratio WB / WA of the width WB of the linear laser irradiation mark on the back surface B of the laser irradiated surface A to the width WA is preferably 0.57 or less (including 0). Further, the width ratio WB / WA is preferably 0.55 or less, more preferably 0.54 or less, more preferably 0.52 or less, and more preferably 0.50 or less. The width ratio WB / WA may be 0. The above-mentioned width ratio WB / WA being 0 means that no linear laser irradiation mark is observed on the back surface B of the laser irradiated surface A.
[0120] The Fe-based amorphous alloy strip of the second embodiment of the present disclosure has a first surface and a second surface. The Fe-based amorphous alloy strip has a plurality of continuous linear laser irradiation marks at least on the first surface. The linear laser irradiation marks are arranged in a direction orthogonal to the casting direction of the Fe-based amorphous alloy strip. The linear laser irradiation marks are molten and solidified portions that are melted and solidified by irradiating the first surface with laser, and extend from the first surface to the second surface. The width ratio WB / WA of the length in the casting direction of the linear laser irradiation marks on the second surface, i.e., the width WB, to the length in the casting direction of the linear laser irradiation marks on the first surface, i.e., the width WA, is less than 0.57.
[0121] The target magnetic properties can be obtained by setting the width ratio WB / WA of the width WB to the width WA to 0.57 or less (including 0). For example, an Fe-based amorphous alloy ribbon having an iron loss of 0.150 W / kg or less at a frequency of 60 Hz and a magnetic flux density of 1.45 T can be obtained.
[0122] The Fe-based amorphous alloy thin strip of the third embodiment of the present disclosure has a first surface and a second surface. The Fe-based amorphous alloy thin strip has a plurality of continuous linear laser irradiation marks at least on the first surface. The linear laser irradiation marks are arranged in a direction orthogonal to the casting direction of the Fe-based amorphous alloy thin strip. The length of the linear laser irradiation marks in the casting direction on the first surface, i.e., the width WA, is not less than 28.5 μm and not more than 90 μm.
[0123] When the width WA is 28.5 μm or more and 90 μm or less, target magnetic properties can be obtained. For example, an Fe-based amorphous alloy ribbon having an iron loss of 0.150 W / kg or less under the conditions of a frequency of 60 Hz and a magnetic flux density of 1.45 T can be obtained.
[0124] When a linear laser irradiation mark is formed on the laser-irradiated surface A of the Fe-based amorphous alloy thin strip, if the energy of the laser reaches or exceeds a predetermined level, the energy of the laser irradiated to surface A is transferred to the back surface B, and a linear laser irradiation mark is also formed on the back surface B.
[0125] When observing the linear laser irradiation mark on the back surface B, if the laser energy is too large, stress folds are formed at the edges of the linear laser irradiation mark on the back surface B. In a state where such stress folds are formed, a low-loss Fe-based amorphous alloy ribbon cannot be obtained.
[0126] Therefore, in order to avoid the formation of the above-mentioned stress folds, it is preferable to irradiate the laser with appropriate energy so as to prevent the stress folds from being formed at the edge of the linear laser irradiation mark on the back surface B.
[0127] Therefore, a study was conducted to obtain a linear laser irradiation mark in which a state in which stress wrinkles are not formed at the edge of the linear laser irradiation mark on the back surface B can be obtained.
[0128] As a result, it was found that if the width ratio WB / WA of the linear laser irradiation mark on the laser-irradiated surface A of the Fe-based amorphous alloy thin strip to the width WA of the linear laser irradiation mark on the laser-irradiated surface A is less than 0.57 (including 0), a state in which no stress wrinkles are formed at the edge of the linear laser irradiation mark on the back side B can be obtained.
[0129] In order to obtain the above-mentioned first mode, second mode, or third mode, the energy of the irradiated laser is set to an appropriate value. The energy of the irradiated laser is appropriately set in consideration of the scanning speed of the laser and the thickness of the alloy strip. For example, it is preferred that the laser density is set to 5 J / m or more and 35 J / m or less.
[0130] In the present disclosure, a linear laser irradiation mark is formed by irradiating a laser using a CW (continuous wave) oscillation mode. The linear laser irradiation mark is a portion that has been melted and solidified by laser irradiation, and the appearance state (color, shape) has changed compared to the portion that has not been irradiated by the laser. That is, the portion whose appearance state has changed is the linear laser irradiation mark (melted and solidified portion).
[0131] The width of the portion where the appearance state has changed (the length in the direction perpendicular to the direction in which the continuous linear shape extends) is defined as the width of the linear laser irradiation mark (molten solidified portion).
[0132] The linear laser irradiation marks formed by irradiation with laser light using the above-mentioned CW (continuous wave) oscillation system are different from the collection of dot-shaped laser irradiation marks using pulsed laser light.
[0133] In the past, methods for subdividing magnetic domains by laser irradiation were known, but these methods usually used pulsed lasers to form point-shaped laser irradiation marks. However, the method using pulsed lasers has problems in productivity due to the following reasons, and is not suitable for low-cost production.
[0134] For example, in the case of high-speed machining, the oscillation frequency needs to be increased, but the oscillation frequency cannot be increased while maintaining the pulse energy and pulse width.
[0135] In the case of laser processing using a CW (continuous wave) oscillation method, productivity can be easily improved by simply oscillating the laser continuously, thereby increasing the output of the oscillator. Thus, an Fe-based amorphous alloy thin strip with desired characteristics can be obtained without high cost. For example, an Fe-based amorphous alloy thin strip with reduced iron loss under the conditions of a frequency of 60 Hz and a magnetic flux density of 1.45 T can be obtained.
[0136] In the present disclosure, the linear laser irradiation mark is formed by irradiating a laser using a CW (continuous wave) oscillation method, and is formed into a continuous line, although it may be partially interrupted, as long as it is continuous for at least 5 mm.
[0137] Furthermore, by observing the laser irradiation marks, it is possible to distinguish between a dot-shaped laser irradiation mark formed by pulsed laser and a linear laser irradiation mark formed by using a CW (continuous wave) oscillation method.
[0138] The Fe-based amorphous alloy ribbon (hereinafter also referred to as "ribbon") of this embodiment has reduced iron loss CL at a frequency of 60 Hz and a magnetic flux density of 1.45 T. In addition, a Fe-based amorphous alloy ribbon having reduced coercive force Hc (60 Hz, 1.45 T) can be obtained.
[0139] In addition, the increase of the excitation power VA (60 Hz, 1.45 T) can be suppressed. In addition, an Fe-based amorphous alloy thin strip with a small degree of deformation due to laser irradiation can be obtained. In addition, an Fe-based amorphous alloy thin strip formed by laser irradiation with high productivity can be obtained.
[0140] In addition, the iron loss CL (1kHz, 1T) under the conditions of frequency 1kHz and magnetic flux density 1T is reduced. In addition, the excitation power VA (1kHz, 1T) under the conditions of frequency 1kHz and magnetic flux density 1T can also be reduced. Therefore, the Fe-based amorphous alloy thin strip disclosed in the present invention is also useful in high-frequency applications.
[0141] The Fe-based amorphous alloy thin strip disclosed in the present invention is a Fe-based amorphous alloy thin strip having a free solidification surface and a roll surface.
[0142] The Fe-based amorphous alloy thin strip having a free solidification surface and a roll surface is a thin strip manufactured (cast) by a single roll method. During casting, the surface that contacts the cooling roll and rapidly solidifies is the roll surface, and the surface opposite to the roll surface (i.e., the surface exposed to the atmosphere during casting) is the free solidification surface.
[0143] Regarding the single roll method, known documents such as International Publication No. 2012 / 102379 may be appropriately referred to.
[0144] The Fe-based amorphous alloy thin strip disclosed herein may be a thin strip in a state of not being cut after casting (for example, a roll body wound in a roll shape after casting), or may be a thin strip slice cut into a desired size after casting.
[0145] Figure 1 A schematic diagram showing a Fe-based amorphous alloy ribbon according to the present embodiment is shown. Figure 1 In the embodiment, a plurality of linear laser irradiation marks 12 are formed on the free solidification surface (or roll surface) of the Fe-based amorphous alloy thin strip 10 . Figure 1In the figure, the left-right direction (arrow direction of L1) corresponds to the casting direction, and the up-down direction (arrow direction of W1) corresponds to the width direction of the thin strip. The linear laser irradiation marks 12 are arranged along the width direction orthogonal to the casting direction of the thin strip. L1 represents the length of the thin strip, W1 represents the width of the thin strip, and LP1 represents the line interval of the linear laser irradiation marks.
[0146] The continuous linear laser irradiation mark is preferably a straight line. Since it is formed by scanning the laser irradiation using the CW oscillation method, a slight fluctuation occurs, but a substantially straight linear laser irradiation mark is formed.
[0147] In addition, the molten solidified portion of the present disclosure is preferably amorphous. If the molten solidified portion is crystallized, the magnetic properties will deteriorate.
[0148] In the present disclosure, the linear laser irradiation marks are arranged along the direction of the width direction orthogonal to the casting direction of the Fe-based amorphous alloy thin strip. In addition, the linear laser irradiation marks are preferably formed in the width direction of the thin strip in a manner including the "central portion in the width direction" described later. Here, the "casting direction" refers to the direction corresponding to the circumferential direction of the cooling roller when casting the Fe-based amorphous alloy thin strip, in other words, the direction corresponding to the long side direction of the Fe-based amorphous alloy thin strip after casting and before cutting. Thus, the direction orthogonal to the long side direction becomes the width direction of the thin strip.
[0149] It should be noted that in the cut thin strip, the direction of the "casting direction" can also be confirmed by observing the free solidification surface and / or roller surface of the thin strip. For example, fine stripes along the casting direction will be observed on the free solidification surface and / or roller surface of the thin strip. In addition, the direction orthogonal to the casting direction is the width direction.
[0150] In the Fe-based amorphous alloy strip of the embodiment, when the interval between adjacent linear laser irradiation marks among a plurality of linear laser irradiation marks at the center of the width direction orthogonal to the casting direction of the Fe-based amorphous alloy strip is set as the line interval, the line interval is preferably 2 mm to 200 mm. The line interval is the line interval on the laser irradiated surface A.
[0151] It should be noted that the width direction refers to a direction perpendicular to the casting direction of the Fe-based amorphous alloy ribbon.
[0152] In addition, when linear laser irradiation marks are formed on both the free solidification surface and the roller surface of the thin strip by laser irradiation, the line interval is measured based on the linear laser irradiation marks on both surfaces when the thin strip is viewed through. For example, when linear laser irradiation marks are formed by alternately irradiating the two surfaces with laser in the casting direction of the thin strip, the objects of "linear laser irradiation marks adjacent to each other" are linear laser irradiation marks irradiated on one surface and linear laser irradiation marks irradiated on the other surface and adjacent in the casting direction.
[0153] If the wire interval is less than 2 mm, reduction in iron loss cannot be expected.
[0154] By setting the wire spacing to 200 mm or less, the iron loss measured under the conditions of a frequency of 60 Hz and a magnetic flux density of 1.45 T is excellently reduced.
[0155] The line spacing is more preferably 3.5 mm or more, more preferably 5 mm or more, and more preferably 10 mm or more. In addition, it is more preferably 100 mm or less, more preferably 80 mm or less, and more preferably 60 mm or less. Furthermore, it can be narrowed to 50 mm or less, 40 mm or less, or 30 mm or less.
[0156] The directions of the plurality of linear laser irradiation marks are preferably substantially parallel, but are not limited to being substantially parallel. The directions of the plurality of linear laser irradiation marks may be parallel or non-parallel.
[0157] The "central part in the width direction" of the Fe-based amorphous alloy thin strip can be set as a part having a certain degree of width from the center in the width direction toward the two ends in the width direction. For example, the range of the area from the center in the width direction toward the two ends in the width direction, where the "certain degree of width" reaches 1 / 5 of the total width (1 / 5 from the center to one end, the length of the central part in the width direction is 1 / 5 of the total width direction) can be set as the central part. Therefore, it is preferred that from the center in the width direction toward the two ends in the width direction, in the area of 1 / 5 from the center to each end, that is, in the area where the length of the central part in the width direction reaches 1 / 5 of the total width, the line spacing is in the range of 2mm to 200mm. It is preferred that in the range of the area where the length of the central part in the width direction reaches 1 / 4 of the total width, the line spacing is in the range of 2mm to 200mm. It is further preferred that in the range of the area where the length of the central part in the width direction reaches 1 / 2 of the total width, the line spacing is in the range of 2mm to 200mm.
[0158] As an embodiment of the present disclosure, a plurality of linear laser irradiation marks may be arranged in a non-parallel direction relative to a width direction orthogonal to the casting direction of the Fe-based amorphous alloy ribbon.
[0159] That is, the angle formed by the direction of each of the plurality of linear laser irradiation marks and the width direction of the Fe-based amorphous alloy ribbon can be larger than 10°, and the linear laser irradiation marks can intersect the casting direction at an acute or obtuse inclination angle.
[0160] As an embodiment of the present disclosure, it is preferable that the directions of the plurality of linear laser irradiation marks are substantially parallel to the direction orthogonal to the casting direction and the thickness direction of the Fe-based amorphous alloy ribbon.
[0161] The meaning that the respective directions of the multiple linear laser irradiation marks are approximately parallel to the direction perpendicular to the casting direction and thickness direction of the Fe-based amorphous alloy strip is that the angle formed by the respective directions of the multiple linear laser irradiation marks and the direction perpendicular to the casting direction and thickness direction of the Fe-based amorphous alloy strip is less than 10°.
[0162] However, the plurality of linear laser irradiation marks are not limited to being substantially parallel.
[0163] Furthermore, as an embodiment of the present disclosure, it is preferable that the directions of the plurality of linear laser irradiation marks are substantially parallel to the width direction of the Fe-based amorphous alloy ribbon.
[0164] The directions of the plurality of linear laser irradiation marks being substantially parallel to the width direction of the Fe-based amorphous alloy ribbon means that the angle formed by the directions of the plurality of linear laser irradiation marks and the width direction of the Fe-based amorphous alloy ribbon is less than 10°.
[0165] However, the plurality of linear laser irradiation marks are not limited to being substantially parallel.
[0166] As described above, the direction of the linear laser irradiation mark may not be parallel to the direction orthogonal to the casting direction of the Fe-based amorphous alloy thin strip, and the direction of the linear laser irradiation mark relative to the angle formed by the direction orthogonal to the casting direction of the Fe-based amorphous alloy thin strip may have an inclination angle greater than 10°. In this way, even if there is an inclination angle greater than 10°, it is interpreted that the linear laser irradiation mark is arranged along the direction orthogonal to the casting direction of the Fe-based amorphous alloy thin strip. The inclination angle is preferably less than 45°, more preferably less than 40°, more preferably less than 30°, and more preferably less than 20°. It is most preferably less than 10°.
[0167] The Fe-based amorphous alloy thin strip disclosed herein may have one linear laser irradiation mark in the width direction of the thin strip, or may have two or more linear laser irradiation marks in the width direction of the thin strip. It should be noted that when there are multiple linear laser irradiation marks in the width direction and the multiple linear laser irradiation marks are arranged in a straight line, they can be regarded as one linear laser irradiation mark.
[0168] Specifically, the Fe-based amorphous alloy strip disclosed in the present invention can be in the following forms: (1) a form having a row of multiple linear laser irradiation marks arranged in the casting direction of the Fe-based amorphous alloy strip in the width direction orthogonal to the casting direction (hereinafter referred to as a single-row group); (2) a form having multiple rows of multiple linear laser irradiation marks arranged in the casting direction of the Fe-based amorphous alloy strip in the width direction orthogonal to the casting direction (hereinafter referred to as a multi-row group).
[0169] Hereinafter, a plurality of linear laser irradiation mark rows provided in the casting direction of the Fe-based amorphous alloy thin strip are also referred to as “irradiation mark groups”.
[0170] In the latter multiple-row group, there are multiple irradiation mark groups in the width direction of the thin strip, and between the multiple groups, the positions of the linear laser irradiation marks do not need to be located on the same line in the width direction, and the linear laser irradiation marks can be in a positional relationship that is staggered in the casting direction. For example, when there are two irradiation mark groups in the width direction of the thin strip, the multiple linear laser irradiation marks arranged in one group and the multiple linear laser irradiation marks arranged in the other group can be in a positional relationship that is staggered a certain distance in the casting direction and alternately exists with each other.
[0171] The line interval in the present disclosure is a value obtained as follows.
[0172] As in (1) above, when there is a row of multiple linear laser irradiation marks arranged in the casting direction in the width direction perpendicular to the casting direction (single row group), the line spacing can be measured at 5 points selected arbitrarily from the spacing between two linear laser irradiation marks adjacent to each other in the casting direction, and the average value of the measured values is taken. In this case, the multiple linear laser irradiation marks constituting the single row group are preferably present at a certain interval, but may be present at any interval.
[0173] In addition, as in (2) above, in the case where there are multiple rows of multiple linear laser irradiation marks (multiple rows) arranged in the casting direction in the width direction orthogonal to the casting direction, the line spacing can be taken as the value obtained by further averaging the value (average value) of each "irradiation mark group" in the multiple rows obtained in the same way as the above method. In this case, the multiple linear laser irradiation marks constituting each "irradiation mark group" are preferably present at a certain interval, but can also exist at any interval. It should be noted that when one row in the multiple rows does not reach the central part in the width direction, its linear laser irradiation marks can be assumed to be extended to the central part in the width direction, thereby obtaining the interval in the central part in the width direction.
[0174] In addition, the ratio of the length of the linear laser irradiation mark in the width direction to the total length of the Fe-based amorphous alloy strip in the width direction is preferably 10% to 50% in the direction from the center in the width direction toward both ends in the width direction. It should be noted that the "%" here is based on the total length of the Fe-based amorphous alloy strip in the width direction as 100%.
[0175] It should be noted that when the direction of the linear laser irradiation mark is inclined relative to the width direction, the value obtained by converting the portion where the linear laser irradiation mark is formed into the length in the width direction of the thin strip is set as the length in the width direction of the linear laser irradiation mark, rather than the length of the inclined linear laser irradiation mark itself.
[0176] The ratio of the length in the width direction of 50% means that the linear laser irradiation mark starts from the center of the Fe-based amorphous alloy thin strip in the width direction and reaches one end and the other end in the width direction. That is, the linear laser irradiation mark is formed from one end to the other end in the width direction of the thin strip.
[0177] For example, when the direction of the linear laser irradiation mark is parallel to the width direction of the Fe-based amorphous alloy ribbon, the total length of the linear laser irradiation mark of the Fe-based amorphous alloy ribbon in the width direction corresponds to the total width of the Fe-based amorphous alloy ribbon.
[0178] In addition, the ratio of the length in the width direction of 10% means that the linear laser irradiation mark starts from the center of the width direction of the Fe-based amorphous alloy thin strip and has a length of 10% in the directions toward the two ends in the width direction, that is, there is a linear laser irradiation mark with a length of 20% of the length of the Fe-based amorphous alloy thin strip in the central area of the Fe-based amorphous alloy thin strip in the width direction. In other words, it means that the linear laser irradiation mark is formed in a manner that leaves a blank space of 40% relative to the total length in the width direction at both ends of the width direction of the Fe-based amorphous alloy thin strip. It is more preferred that the ratio of the length of the linear laser irradiation mark in the width direction of the Fe-based amorphous alloy thin strip in the total length in the width direction of the thin strip is 25% or more in the direction from the center of the width direction toward the two ends in the width direction.
[0179] Furthermore, the linear laser irradiation marks are preferably formed in at least six regions in the center in the width direction, excluding two regions at both ends from eight regions obtained by dividing the Fe-based amorphous alloy ribbon into eight equal regions in the width direction.
[0180] In addition, when multiple rows of linear laser irradiation marks are provided, the multiple rows can be combined and the length of the linear laser irradiation marks occupied by the total length of the thin strip in the width direction can be evaluated at the position closest to the two ends in the width direction.
[0181] It should be noted that the linear laser irradiation marks of the present disclosure have the above-mentioned characteristics. However, when a large number of linear laser irradiation marks are formed in a Fe-based amorphous alloy ribbon, for example, even if not all of the linear laser irradiation marks have the above-mentioned constitution of the present disclosure, the effect of the present disclosure can be obtained. It is preferred that among all the linear laser irradiation marks, more than 60% of the linear laser irradiation marks have the above-mentioned constitution of the present disclosure. Further, it is preferred that more than 70% of the linear laser irradiation marks have the above-mentioned constitution of the present disclosure. Further, it is preferred that more than 80% of the linear laser irradiation marks have the above-mentioned constitution of the present disclosure. Further, it is preferred that more than 90% of the linear laser irradiation marks have the above-mentioned constitution of the present disclosure. Further, it is preferred that all the linear laser irradiation marks have the above-mentioned constitution of the present disclosure.
[0182] <Roughness of free solidification surface (maximum cross-sectional height Rt)>
[0183] In addition, as described in, for example, International Publication No. 2012 / 102379, conventionally, an operation of reducing iron loss by providing corrugated irregularities on a free solidification surface has been performed.
[0184] However, according to the study by the present inventors, it was found that the wave-like irregularities may cause an increase in the excitation power measured under the conditions of a frequency of 60 Hz and a magnetic flux density of 1.45 T.
[0185] Therefore, from the viewpoint of suppressing an increase in the exciting power measured under the conditions of a frequency of 60 Hz and a magnetic flux density of 1.45 T, it is preferable to reduce the wave-like irregularities as much as possible.
[0186] Specifically, the maximum cross-sectional height Rt of the portion other than the plurality of linear laser irradiation marks on the free solidification surface is preferably 3.0 μm or less.
[0187] The maximum cross-sectional height Rt being 3.0 μm or less means that the free solidification surface has no wavy irregularities or the wavy irregularities are reduced.
[0188] In this specification, regarding the maximum cross-sectional height Rt in the portion other than the multiple linear laser irradiation marks on the free solidification surface, for the portion other than the multiple linear laser irradiation marks on the free solidification surface, the evaluation length is set to 4.0 mm, the cutoff value is set to 0.8 mm, and the cutoff type is set to 2RC (phase compensation) for measurement (evaluation) in accordance with JIS B 0601:2001. Here, the direction of the evaluation length is set to the casting direction of the Fe-based amorphous alloy thin strip. In addition, in detail, the above measurement with the evaluation length set to 4.0 mm is performed by measuring 5 times continuously with a cutoff value of 0.8 mm.
[0189] The maximum cross-sectional height Rt of the portion other than the plurality of linear laser irradiation marks on the free solidification surface is more preferably 2.5 μm or less.
[0190] In addition, the lower limit of the maximum cross-sectional height Rt is not particularly limited, but from the viewpoint of the production suitability of the Fe-based amorphous alloy ribbon, the lower limit of the maximum cross-sectional height Rt is preferably 0.8 μm, and more preferably 1.0 μm.
[0191] <Chemical composition>
[0192] The chemical composition of the Fe-based amorphous alloy strip disclosed in the present invention is not particularly limited, as long as it is the chemical composition of the Fe-based amorphous alloy (i.e., a chemical composition with Fe (iron) as the main component). However, from the viewpoint of more effectively obtaining the effects brought about by the Fe-based amorphous alloy strip disclosed in the present invention, the chemical composition of the Fe-based amorphous alloy strip disclosed in the present invention is preferably the following chemical composition A. Chemical composition A as a preferred chemical composition is the following chemical composition: composed of Fe, Si, B and impurities, when the total content of Fe, Si and B is set to 100 atomic %, the content of Fe is 78 atomic % or more, the content of B is 10 atomic % or more, and the total content of B and Si is 17 atomic % to 22 atomic %.
[0193] Hereinafter, the chemical composition A will be described in more detail.
[0194] In the chemical composition A, the content of Fe is 78 atomic % or more.
[0195] Fe (iron) has an amorphous structure and is one of the transition metals with the largest magnetic moment. It is the bearer of magnetism in Fe-Si-B amorphous alloys.
[0196] When the Fe content is 78 atomic % or more, the saturation magnetic flux density (Bs) of the Fe-based amorphous alloy ribbon can be increased (for example, a Bs of about 1.6 T can be achieved). Furthermore, the preferred magnetic flux density B0.1 (1.52 T or more) can be easily achieved.
[0197] The Fe content is preferably 80 atomic % or more, more preferably 80.5 atomic % or more, and even more preferably 81.0 atomic % or more, and is preferably 82.5 atomic % or less, and even more preferably 82.0 atomic % or less.
[0198] In the chemical composition A, the content of B is 10 atomic % or more.
[0199] B (boron) is an element that contributes to amorphous formation. When the content of B is 10 atomic % or more, the amorphous forming ability is further improved.
[0200] When the B content is 10 atomic % or more, the magnetic domains are easily oriented in the casting direction, and the magnetic flux density (B0.1) is easily improved by widening the magnetic domain width.
[0201] The B content is preferably 11 atomic % or more, more preferably 12 atomic % or more.
[0202] The upper limit of the B content also depends on the total content of B and Si described later, but is preferably 16 atomic %.
[0203] In the chemical composition A, the total content of B and Si is 17 atomic % to 22 atomic %.
[0204] Si (silicon) is an element that segregates on the surface in the molten metal state and has the effect of preventing the molten metal from oxidizing. Furthermore, Si also acts as an auxiliary agent for amorphous formation, has the effect of increasing the glass transition temperature, and forms a more thermally stable amorphous phase.
[0205] When the total content of B and Si is 17 atomic % or more, the above-mentioned effect of Si is effectively exhibited.
[0206] In addition, when the total content of B and Si is 22 atomic % or less, a larger amount of Fe as a magnet can be ensured, which is advantageous in increasing the saturation magnetic flux density Bs and increasing the magnetic flux density B0.1. Preferably, the total content of B and Si is 20 atomic % or less, which can be appropriately determined by the relationship with the Fe content.
[0207] The Si content is preferably 2.0 atomic % or more, more preferably 2.4 atomic % or more, and further preferably 3.5 atomic % or more.
[0208] The upper limit of the Si content also depends on the total content of B and Si, but is preferably 6.0 atomic %.
[0209] In the above-mentioned chemical composition A, from the perspective of the iron loss described later and further improving the excitation power, the more preferred chemical composition of the Fe-based amorphous alloy thin strip is composed of Fe, Si, B and impurities. When the total content of Fe, Si and B is set to 100 atomic %, the Fe content is more than 80 atomic %, the B content is more than 12 atomic %, and the total content of B and Si is 17 atomic % to 20 atomic %.
[0210] Chemical composition A contains impurities.
[0211] In this case, the impurities contained in the chemical composition A may be only one kind or may be two or more kinds.
[0212] Impurities include all elements other than Fe, Si and B. Specifically, for example, C, Ni, Co, Mn, O, S, P, Al, Ge, Ga, Be, Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, rare earth elements, etc.
[0213] These elements may be contained in a total amount of 1.5% by mass or less relative to the total mass of Fe, Si and B. The upper limit of the total content of these elements is preferably 1.0% by mass or less, more preferably 0.8% by mass or less, and further preferably 0.75% by mass or less. It should be noted that these elements may also be added within this range.
[0214] <Thickness>
[0215] The thickness of the Fe-based amorphous alloy ribbon disclosed in the present invention is not particularly limited, and the thickness is preferably 18 μm to 35 μm.
[0216] A thickness of 18 μm or more is advantageous in suppressing the waviness of the Fe-based amorphous alloy ribbon and improving the occupancy rate. A more preferred thickness is 20 μm or more.
[0217] A thickness of 35 μm or less is advantageous in terms of suppressing embrittlement and magnetic saturation of the Fe-based amorphous alloy ribbon, and a more preferred thickness of 30 μm or less.
[0218] <Iron loss CL>
[0219] As described above, in the Fe-based amorphous alloy ribbon of the present disclosure, the magnetic domains are subdivided by forming linear laser irradiation marks, thereby reducing the iron loss CL under the conditions of a frequency of 60 Hz and a magnetic flux density of 1.45 T.
[0220] The iron loss CL under the conditions of a frequency of 60 Hz and a magnetic flux density of 1.45 T is preferably 0.150 W / kg or less, more preferably 0.140 W / kg or less, and further preferably 0.130 W / kg or less.
[0221] The lower limit of the iron loss CL under the conditions of a frequency of 60 Hz and a magnetic flux density of 1.45 T is not particularly limited, but is preferably 0.050 W / kg from the viewpoint of production suitability of the Fe-based amorphous alloy ribbon.
[0222] In addition, in the Fe-based amorphous alloy thin strip disclosed in the present invention, the iron loss CL under the conditions of frequency 1kHz and magnetic flux density 1T is also reduced. The iron loss CL under the conditions of frequency 1kHz and magnetic flux density 1T is preferably 8.6W / kg or less. It is more preferably 8.0W / kg or less, and further preferably 7.0W / kg or less.
[0223] Furthermore, in the Fe-based amorphous alloy ribbon disclosed herein, the iron loss CL is also reduced at a frequency of 50 Hz and a magnetic flux density of 1.45 T. In the Fe-based amorphous alloy ribbon disclosed herein, the iron loss CL at a frequency of 50 Hz and a magnetic flux density of 1.45 T is preferably 0.120 W / kg or less.
[0224] The core loss CL in the Fe-based amorphous alloy ribbon is measured in accordance with JIS 7152 (1996 edition).
[0225] <Excitation power VA>
[0226] As described above, in the Fe-based amorphous alloy thin strip disclosed in the present invention, the increase in the excitation power VA under the conditions of a frequency of 60 Hz and a magnetic flux density of 1.45 T is suppressed. If the height difference of the linear laser irradiation mark becomes larger, there is a tendency that the excitation power VA also becomes larger. For example, by making the height difference less than 2.5 μm, a significant increase in the excitation power VA can be suppressed.
[0227] In addition, in the Fe-based amorphous alloy thin strip disclosed in the present invention, the excitation power VA under the conditions of frequency 1kHz and magnetic flux density 1T is reduced. The excitation power VA under the conditions of frequency 1kHz and magnetic flux density 1T is preferably 8.7VA / kg or less. More preferably, it is 8.0VA / kg or less, and further preferably, it is 7.5VA / kg or less.
[0228] <Coercive force Hc>
[0229] As described above, in the Fe-based amorphous alloy ribbon disclosed in the present invention, the coercive force Hc under the conditions of a frequency of 60 Hz and a magnetic flux density of 1.45 T is reduced.
[0230] <Ratio〔Operating magnetic flux density Bmax / Saturation magnetic flux density Bs〕>
[0231] As described above, the Fe-based amorphous alloy ribbon of the present disclosure can suppress the iron loss and the excitation power at a higher magnetic flux density, that is, a magnetic flux density of 1.45 T than the conventional magnetic flux density of 1.3 T.
[0232] Therefore, even when used under an operating magnetic flux density Bmax under conditions where the ratio [operating magnetic flux density Bmax / saturation magnetic flux density Bs] (hereinafter also referred to as "Bmax / Bs ratio") is higher than before, iron loss and excitation power can be suppressed.
[0233] In this regard, a previous example involved an Fe-based amorphous alloy thin strip used under conditions of a saturation magnetic flux density Bs of 1.56 T and an operating magnetic flux density Bmax of 1.35 T (i.e., Bmax / Bs ratio = 0.87) (see, for example, IEEE TRANSACTIONS ON MAGNETICS Vol 44, No 11, Nov. 2008, pp. 4104-4106 (especially p. 4106)).
[0234] In contrast, the Fe-based amorphous alloy ribbon of the present disclosure, for example, has the chemical composition (Fe 82 4B 14 ) has a Bs of 1.63T. Bs can be uniquely determined based on the chemical composition. In this case, the Fe-based amorphous alloy thin strip of the present disclosure can be used at a Bmax of 1.43T or more (preferably 1.45T to 1.50T). The Bmax / Bs ratio is 0.88 when Bmax is 1.43T, and the Bmax / Bs ratio is 0.92 when Bmax is 1.50T.
[0235] Based on the above reasons, the Fe-based amorphous alloy thin strip disclosed in the present invention is particularly suitable for use in applications where the operating magnetic flux density Bmax satisfies a Bmax / Bs ratio of 0.88 to 0.94 (preferably 0.89 to 0.92).
[0236] The Fe-based amorphous alloy ribbon disclosed herein can suppress increases in iron loss and excitation power even when used at an operating magnetic flux density Bmax satisfying a Bmax / Bs ratio of 0.88 to 0.94 (preferably 0.89 to 0.92).
[0237] The above-mentioned properties (iron loss CL, excitation power VA, coercive force Hc) are the values obtained by heat treating the Fe-based amorphous alloy ribbon by applying a magnetic field in the long side direction of the ribbon. The heat treatment of the Fe-based amorphous alloy ribbon in a magnetic field is for the purpose of relaxing internal stress and aligning the magnetization in the long side direction of the ribbon, and is suitable for obtaining the desired properties. As a heat treatment condition, it can be carried out by keeping it at about 300°C to 400°C for a certain time. The holding time is preferably within 24 hours, and more preferably within 4 hours. The magnetic field in the heat treatment is preferably above 400A / m, and more preferably above 800A / m. In addition, it can be carried out in the atmosphere, in an inert gas such as argon, nitrogen, helium, or in a vacuum. In addition, heat treatment can also be performed after the core is formed.
[0238] Furthermore, the Fe-based amorphous alloy ribbon of the present disclosure preferably has excellent properties in a state after the linear laser irradiation marks are formed and before heat treatment is performed.
[0239] For example, before heat treatment, the coercive force Hc of the DC BH curve measured at a maximum applied magnetic field of 800 A / m is preferably 5.0 A / m or less. The coercive force Hc is preferably 4.9 A / m or less, and more preferably 4.8 A / m or less. In addition, the squareness ratio [residual magnetic flux density Br / maximum magnetic flux density Bm] at this time is preferably 40% or less.
[0240] In this way, when the state before heat treatment is excellent, the holding time during heat treatment can be shortened, and embrittlement after heat treatment is not easily caused. As a result, the operability when making the transformer core becomes better. In addition, large iron cores and laminated iron cores for electronic components are sometimes used in a state without heat treatment due to the problem of embrittlement. In this case, it is advantageous to have excellent characteristics in the state before heat treatment.
[0241] <Method for producing Fe-based amorphous alloy ribbon>
[0242] The Fe-based amorphous alloy thin strip of the present disclosure can be preferably produced by the following production method.
[0243] The manufacturing method of the embodiment is a method for manufacturing a Fe-based amorphous alloy thin strip as follows, wherein:
[0244] A raw material thin strip composed of an Fe-based amorphous alloy and having a free solidification surface and a roll surface is irradiated with a laser using a CW (continuous wave) oscillation method to obtain an Fe-based amorphous alloy thin strip having a plurality of linear laser irradiation marks,
[0245] The laser density of the CW (continuous wave) laser is 5 J / m or more and 35 J / m or less.
[0246] The linear laser irradiation mark is a continuous line, and is provided along a width direction of the Fe-based amorphous alloy ribbon that is perpendicular to the casting direction.
[0247] Hereinafter, the step of forming a plurality of continuous linear laser irradiation marks by using CW (continuous wave) oscillation laser light is also referred to as a “laser processing step”.
[0248] In the manufacturing method of this embodiment, other steps other than the laser processing step may be included as needed. For example, before the laser processing step, there may be a step of preparing a raw material strip (raw material preparation step). In addition, when the raw material preparation step includes a casting step of the raw material strip, the casting step of the raw material strip and the laser processing step may be continuous.
[0249] <Raw material preparation process>
[0250] In this embodiment, a raw material preparation step may be provided before the laser processing step. The raw material preparation step is a step of preparing a raw material thin strip having a free solidification surface and a roll surface.
[0251] The raw material strip mentioned here can be a strip in a state of not being cut after casting (for example, a roll body wound in a roll shape after casting), or a strip slice cut into a desired size after casting. It should be noted that the cut strip slice is also equivalent to the Fe-based amorphous alloy strip disclosed in the present invention.
[0252] The raw material ribbon can be said to be the Fe-based amorphous alloy ribbon of the present disclosure at a stage before the linear laser irradiation mark is formed.
[0253] The free solidification surface and the roll surface of the raw material thin strip are respectively synonymous with the free solidification surface and the roll surface of the Fe-based amorphous alloy thin strip of the present disclosure.
[0254] Preferred aspects of the raw material ribbon (eg, preferred chemical composition, preferred Rt) are the same as those of the Fe-based amorphous alloy ribbon disclosed herein, except for the presence or absence of the linear laser irradiation mark.
[0255] The raw material preparation step may be a step of merely preparing a pre-cast (ie, already manufactured) raw material strip for use in the laser processing step, or may be a step of newly casting a raw material strip.
[0256] Furthermore, the raw material preparation step may be a step of performing at least one of casting the raw material strip and cutting strip pieces from the raw material strip.
[0257] <Laser processing>
[0258] In the laser processing step of this embodiment, for at least one of the free solidification surface and the roller surface of the raw material thin strip, multiple continuous linear laser irradiation marks are formed by using CW (continuous wave) oscillation laser processing (i.e., by irradiating with CW (continuous wave) oscillation laser).
[0259] Preferred aspects of the linear laser irradiation marks formed by the laser processing step (preferred line intervals, height differences, etc.) are the same as the preferred aspects of the linear laser irradiation marks in the Fe-based amorphous alloy ribbon of the present disclosure described above.
[0260] As described above, each of the plurality of linear laser irradiation marks is a mark to which energy is imparted by laser irradiation, and the effect of reducing the iron loss due to laser irradiation can be obtained.
[0261] Therefore, the conditions of the laser in the laser processing step are not particularly limited, but the preferred conditions are as follows.
[0262] By controlling the irradiation energy of the laser with respect to the thickness of the Fe-based amorphous alloy ribbon, the width of the linear laser irradiation mark and the uneven state of the surface can be controlled.
[0263] In the laser processing step, the laser density (also referred to as "laser line density") for forming a linear laser irradiation mark is preferably 5 J / m or more and 35 J / m or less. A more preferred lower limit is 6 J / m, more preferably 7 J / m, more preferably 8 J / m, and more preferably 10 J / m. In addition, a more preferred upper limit is 31 J / m, more preferably 30 J / m, more preferably 28 J / m, and more preferably 25 J / m.
[0264] In laser processing, when forming the laser irradiation mark, CW laser is irradiated by scanning in the ribbon width direction.
[0265] As the laser light source, YAG laser, CO2 gas laser, fiber laser, diode laser, etc. can be used. Among them, fiber laser is preferred from the aspect of being able to stably irradiate high-quality laser for a long time. In the case of a single-mode fiber laser, M2 (M-Square) indicating the beam quality is about 1.3 or less.
[0266] In a fiber laser, the laser introduced into the optical fiber oscillates according to the principle of FBG (Fiber Bragg Grating) through the diffraction gratings at both ends of the optical fiber. Since the laser is excited in a long and thin optical fiber, there is no problem of thermal lens effect in which the beam quality is reduced due to the temperature gradient generated inside the crystal. Furthermore, since the core is as thin as several microns, the laser can propagate in a single mode even at high output, the beam diameter becomes narrower, and a high-energy-density laser can be obtained. Moreover, since the focal depth is deep, laser irradiation marks can be formed with good precision on a wide ribbon (for example, a ribbon width of 200 mm or more).
[0267] The wavelength of the laser light may be about 250 nm to 10600 nm depending on the laser light source, among which the wavelength of 900 to 1100 nm is suitable because it is sufficiently absorbed in the alloy ribbon.
[0268] The beam diameter of the laser light is preferably from 10 μm to 500 μm, and more preferably from 25 μm to 100 μm.
[0269] In addition, the laser processing step can be a process of laser processing the raw material thin strip before winding after casting by a single roller method, or a process of laser processing the raw material thin strip unwound from the wound raw material thin strip (roller body), or a process of laser processing the thin strip sheet cut from the wound raw material thin strip.
[0270] When the laser processing step is a step of laser processing a raw material strip after casting by a single roll method and before winding, for example, the laser processing step can be performed using a system in which a laser processing device is arranged between a cooling roll and a winding roll.
[0271] Furthermore, the scanning speed of the CW laser is preferably 0.2 m / sec or more from the perspective of stability of the CW laser output, and is preferably 4000 m / sec or less from the perspective of hot working the raw material ribbon.
[0272] <Iron core>
[0273] The iron core disclosed in the present invention is obtained by overlapping and stacking a plurality of Fe-based amorphous alloy thin strips disclosed in the present invention. Specifically, the Fe-based amorphous alloy thin strips are stacked and the stacked Fe-based amorphous alloy thin strips are bent and wound. In addition, the iron loss of the iron core disclosed in the present invention under the conditions of a frequency of 60 Hz and a magnetic flux density of 1.45 T is less than 0.240 W / kg. It is preferably less than 0.230 W / kg, more preferably less than 0.200 W / kg, and further preferably less than 0.180 W / kg.
[0274] The lower limit of the iron loss under the conditions of a frequency of 60 Hz and a magnetic flux density of 1.45 T is not particularly limited, but from the viewpoint of the manufacturing suitability of the Fe-based amorphous alloy ribbon, the lower limit of the iron loss is preferably 0.050 W / kg, and more preferably 0.080 W / kg.
[0275] The details of the Fe-based amorphous alloy ribbon disclosed in the present invention are as described above, and a detailed description thereof will be omitted.
[0276] A known method can be applied as the lap winding method.
[0277] The shape of the core of the present disclosure may be circular, rectangular, or the like.
[0278] In addition, the type of the coil wound around the core is not limited and may be appropriately selected based on known contents.
[0279] When manufacturing an iron core, the iron loss value of the raw material (Fe-based amorphous alloy strip) is not directly maintained, and the iron loss value of the iron core becomes greater than the iron loss value of the raw material. It is also called the assembly factor (Building Factor). For example, since stress is applied to the raw material when manufacturing the iron core, the iron loss value becomes larger. However, for the iron core disclosed in the present invention, although the iron loss value increases compared to the raw material, an iron core with extremely low iron loss can also be obtained. In particular, an iron core with low iron loss under the conditions of a frequency of 60 Hz and a magnetic flux density of 1.45 T can be obtained. Furthermore, an iron core with low iron loss can also be obtained under conditions other than the conditions of a frequency of 60 Hz and a magnetic flux density of 1.45 T.
[0280] In addition, the Fe-based amorphous alloy thin strip disclosed in the present invention is not limited to the above-mentioned iron core structure, and can also be used for iron cores and electronic components of other structures. For example, it can be a wound iron core or a laminated iron core. For example, it can also be used for wound magnetic cores for electronic components, cut cores with gaps formed by wound iron cores, laminated materials, etc. These iron cores can be formed by stacking or winding the Fe-based amorphous alloy thin strips disclosed in the present invention.
[0281] <Transformer>
[0282] The transformer disclosed in the present invention comprises an iron core using the Fe-based amorphous alloy thin strips disclosed in the present invention and a coil wound around the iron core. The iron core is formed by bending and winding the stacked Fe-based amorphous alloy thin strips. The iron loss under the conditions of frequency 60 Hz and magnetic flux density 1.45 T is less than 0.240 W / kg.
[0283] The details of the Fe-based amorphous alloy thin strip and the iron core of the present disclosure are as described above, and a detailed description thereof will be omitted.
[0284] The iron core of the present disclosure is obtained by overlapping and stacking a plurality of Fe-based amorphous alloy thin strips of the present disclosure described above, and bending and winding the stacked Fe-based amorphous alloy thin strips. A known method can be applied to the winding method.
[0285] In the transformer disclosed herein, the iron loss at a frequency of 60 Hz and a magnetic flux density of 1.45 T is 0.240 W / kg or less, preferably 0.230 W / kg or less, more preferably 0.200 W / kg or less, and further preferably 0.180 W / kg or less.
[0286] The lower limit of the iron loss under the conditions of a frequency of 60 Hz and a magnetic flux density of 1.45 T is not particularly limited, but from the viewpoint of the manufacturing suitability of the Fe-based amorphous alloy ribbon, the lower limit of the iron loss is preferably 0.050 W / kg, and more preferably 0.080 W / kg.
[0287] The measurement of the iron loss in the transformer of the present disclosure including the wound Fe-based amorphous alloy thin strips will be described later in Examples.
[0288] The shape of the iron core in the transformer of the present disclosure may be any of circular and rectangular shapes. In addition, the type of the coil wound around the iron core is not limited, and any shape may be appropriately selected from known shapes.
[0289] In addition, the iron core in the transformer disclosed in the present invention is not limited to the iron core formed by bending and winding the stacked Fe-based amorphous alloy thin strips. The iron core of the transformer can be appropriately designed according to the application, and can be made into a stacked core, a wound core, etc.
[0290] When the transformer is a single-phase transformer, the no-load loss per unit weight of the core at 50 Hz is preferably 0.15 W / kg or less. Furthermore, the no-load loss per unit weight of the core at 60 Hz is preferably 0.19 W / kg or less.
[0291] When the transformer is a three-phase transformer, the no-load loss per unit weight of the core at 50 Hz is preferably 0.19 W / kg or less. Furthermore, the no-load loss per unit weight of the core at 60 Hz is preferably 0.24 W / kg or less.
[0292] Hereinafter, embodiments of the present disclosure are shown, but the present disclosure is not limited to the following embodiments.
[0293] [Example 1]
[0294] <Manufacturing of raw material ribbon (Fe-based amorphous alloy ribbon before laser processing)>
[0295] Fabricated with Fe 82 4B 14A raw material thin strip with a chemical composition of , a thickness of 25 μm and a width of 210 mm (i.e., an Fe-based amorphous alloy thin strip before laser processing).
[0296] Here, "Fe 82 4B 14 The chemical composition of the present invention refers to a chemical composition consisting of Fe, Si, B and impurities, wherein, when the total content of Fe, Si and B is set to 100 atomic %, the content of Fe is 82 atomic %, the content of B is 14 atomic %, and the content of Si is 4 atomic %.
[0297] The following describes in detail the production of the raw material ribbon.
[0298] In the production of raw material thin strip, Fe 82 4B 14 The molten metal with the chemical composition of 10 ...
[0299] At this time, the atmosphere around the surface of the cooling roll immediately below the slit nozzle where the molten metal pool is formed is set to a non-oxidizing gas atmosphere.
[0300] The slit length of the slit nozzle was set to 210 mm, and the slit width was set to 0.6 mm.
[0301] The material of the cooling roller was set to a Cu-based alloy, and the peripheral speed of the cooling roller was set to 27 m / s.
[0302] The pressure of the ejected molten metal and the nozzle gap (i.e., the gap between the front end of the slit nozzle and the surface of the cooling roller) are adjusted so that the maximum cross-sectional height Rt of the free solidification surface of the manufactured raw material strip (specifically, the maximum cross-sectional height Rt measured along the casting direction of the raw material strip) becomes less than 3.0 μm.
[0303] <Laser processing>
[0304] A sample piece is cut out from the raw material ribbon, and the cut sample piece is subjected to laser processing to obtain a laser processed Fe-based amorphous alloy ribbon piece.
[0305] The following describes the details.
[0306] Figure 1 1 is a schematic plan view schematically showing a free solidification surface of a Fe-based amorphous alloy thin ribbon piece (the thin ribbon 10 ) after laser processing.
[0307] Figure 1The length L1 of the strip 10 shown (i.e., the length of the sample piece cut from the raw material strip) is set to 120 mm, and the width W1 of the strip 10 (i.e., the width of the sample piece cut from the raw material strip) is set to 25 mm. The sample piece is cut in a direction in which the length direction of the sample piece coincides with the length direction (casting direction) of the raw material strip, and the width direction of the sample piece coincides with the width direction of the raw material strip.
[0308] The free solidification surface of the cut sample piece is irradiated with laser light using a CW (continuous wave) oscillation method to form a plurality of linear laser irradiation marks 12 , thereby obtaining a ribbon 10 .
[0309] Specifically, a plurality of linear laser irradiation marks 12 are formed on the free solidification surface of the sample piece (the strip 10 before laser processing. The same shall apply hereinafter) in a direction parallel to the width direction of the sample piece. The linear laser irradiation marks 12 are formed over the entire area in the width direction of the sample piece. That is, the length of the linear laser irradiation marks 12 in the width direction of the sample piece is made 100% relative to the total width of the sample piece. In other words, the ratio of the length of the linear laser irradiation marks 12 in the width direction to the total length of the Fe-based amorphous alloy strip 10 in the width direction is 50% in the direction from the center in the width direction toward the two ends in the width direction.
[0310] The directions of the plurality of linear laser irradiation marks 12 are made parallel to each other.
[0311] The laser processing conditions were changed to produce a plurality of sample sheets. The laser processing conditions are shown in Tables 1 and 3. Tables 1 and 3 show the line spacing LP1 (mm), the scanning speed (m / sec) of the laser in the CW (continuous wave) oscillation mode, and the laser density (J / m). It should be noted that the laser density is obtained by dividing the output of the laser oscillator by the scanning speed, and is an index indicating the intensity of the laser per unit length.
[0312] The irradiation conditions of the CW (continuous wave) laser beam are as follows.
[0313] (CW laser irradiation conditions)
[0314] As a laser oscillator, a fiber laser (YLR-150-1500-QCW) from IPG Optoelectronics was used. The laser medium of this laser oscillator was Yb-doped glass fiber, and the oscillation wavelength was 1064 nm.
[0315] On the other hand, the spot diameter of the laser light on the free solidification surface of the sample piece was adjusted to 37.0 μm. The beam diameter was adjusted using a collimator lens: f100 mm and an fθ lens: focal length 254 mm / processing point distance 297 mm as optical components.
[0316] The beam mode M2 is set to 1.05 (single mode).
[0317] The laser output was set to 0-275W, and the Focus was set to 0mm.
[0318] Here, Focus means the difference (absolute value) between the processing point distance of the focusing lens (297 mm) and the actual distance from the focusing lens to the free solidification surface of the ribbon.
[0319] In addition, between the incident diameter D and the spot diameter D0, the relationship D0=4λf / πD (here, λ represents the wavelength of the laser and f represents the focal distance) holds true. Therefore, as the focal distance of the collimating lens increases (that is, as the incident diameter D increases), the spot diameter D0 tends to decrease.
[0320] <Measurement and evaluation>
[0321] For Fe-based amorphous alloy ribbon after laser processing ( Figure 1 The thin strip 10) was heat treated in a magnetic field (nitrogen atmosphere) at 370°C for 20 minutes at 3000 A / m, and then the following measurements and evaluations were performed. The results are shown in Tables 1 to 4.
[0322] <Maximum cross-sectional height Rt of non-laser processing area>
[0323] For the portion other than the linear laser irradiation mark 12 in the free solidification surface of the Fe-based amorphous alloy strip after laser processing (i.e., the non-laser processing area), the maximum cross-sectional height Rt is measured by setting the evaluation length to 4.0 mm, the cutoff value to 0.8 mm, and the cutoff category to 2RC (phase compensation) in accordance with JIS B 0601:2001. It should be noted that the measurement of the maximum cross-sectional height Rt can also be performed before laser processing. Here, the direction of the evaluation length is set to the casting direction of the raw material strip. In the above measurement with the evaluation length set to 4.0 mm, in detail, it is performed by continuously measuring 5 times with a cutoff value of 0.8 mm.
[0324] The above measurement was performed at three locations in the non-laser processed region with an evaluation length of 4.0 mm, and the average of the three measured values was defined as the maximum cross-sectional height Rt (μm) of this example.
[0325] As a result, the maximum cross-sectional height Rt of each sample piece was in the range of 1.0 to 2.5 μm.
[0326] <Measurement of Iron Loss CL>
[0327] The iron loss CL of the laser processed Fe-based amorphous alloy ribbon was measured using an AC magnetometer with sinusoidal excitation under two conditions: a frequency of 60 Hz and a magnetic flux density of 1.45 T and a frequency of 60 Hz and a magnetic flux density of 1.50 T.
[0328] <Measurement of Excitation Power VA>
[0329] The excitation power VA of the laser processed Fe-based amorphous alloy thin strip was measured by using an AC magnetic measuring device with sinusoidal excitation under two conditions: a frequency of 60 Hz and a magnetic flux density of 1.45 T and a frequency of 60 Hz and a magnetic flux density of 1.50 T.
[0330] <Measurement of coercive force Hc>
[0331] The coercive force Hc of the laser processed Fe-based amorphous alloy ribbon was measured using an AC magnetometer with sinusoidal excitation under two conditions: a frequency of 60 Hz and a magnetic flux density of 1.45 T and a frequency of 60 Hz and a magnetic flux density of 1.50 T.
[0332] <Measurement of the width of the linear laser irradiation mark (melted solidification portion) and observation of stress wrinkles>
[0333] The linear laser irradiation marks on the laser-irradiated surface A and the linear laser irradiation marks on the back side B of the laser-irradiated surface A were observed using a laser microscope, and the width WA of the linear laser irradiation marks (melting and solidification portion) on the laser-irradiated surface A and the width WB of the linear laser irradiation marks on the back side B of the laser-irradiated surface A were measured. It should be noted that the linear laser irradiation marks (melting and solidification portion) are the portions whose appearance state has changed due to melting and solidification, and the width of the portion whose appearance state has changed is set as the width of the linear laser irradiation marks (melting and solidification portion). It should be noted that there are also cases where the linear laser irradiation marks on the back side B of the laser-irradiated surface A are not observed. In this case, the width WB is set to 0 μm.
[0334] In addition, the presence or absence of stress wrinkles at the edge of the linear laser irradiation mark (melted and solidified portion) on the back surface B of the laser irradiated surface A was checked.
[0335] It should be noted that the microscope photographs were taken at a magnification of 1000 times.
[0336] Specifically, the surface shape was photographed using a color 3D laser microscope VK-8710 (manufactured by KEYENCE CORPORATION) and a 50x objective lens CF IC EPI Plan 50X (manufactured by Nikon CORPORATION) (magnification: 1000x (objective lens 50x×monitor magnification 20x)).
[0337] Here, the measured width WA, width WB, and the presence or absence of stress folds are shown in Tables 1 to 6. Note that the observation results of the width WB and stress folds are shown in Tables 5 and 6. Tables 5 and 6 show the results of observing the width WB and stress folds in some of the results shown in Tables 1 to 4, and the same numbers are given to the same samples as in Tables 1 to 4.
[0338] In this embodiment, the width WA and the width WB were measured at the portion where the maximum value was obtained. It should be noted that three portions where the maximum value was obtained were measured and the average value was calculated.
[0339] <Concave-convex state of the linear laser irradiation mark (melted solidification part)>
[0340] The linear laser irradiation marks (molten solidification part) of the laser-irradiated surface A are formed with concavoconvexity on the surface. The concavoconvex state of the above surface is observed in the width direction of the molten solidification part (equivalent to the casting direction). Regarding the observation method, a laser microscope (the above-mentioned color 3D laser microscope VK-8710, the magnification is also the same) is used. Specifically, the profile of the width direction of the linear laser irradiation mark is measured using a laser microscope. Figure 2 A microscope photograph of a linear laser irradiation mark is shown. Figure 2 As shown in FIG. 1 , for the width WA of the linear laser irradiation mark, a width of approximately 30 μm is added to the front and back, and the profile in between (30 μm + width WA + 30 μm) is measured. The above profile is Figure 3 The height difference HL is measured from the profile. If the profile is tilted, the tilt is corrected linearly to be horizontal using the range of 30 μm added before and after, and then measured.
[0341] The concave-convex state of the above surface can be roughly divided into Figure 3 The morphologies of type A, type B, and type C are shown. Figure 3 Although there are actually fine irregularities in each type, the diagram schematically shows the major shape changes. Figure 3 The shape shown is equivalent to the surface state of the cross section of the Fe-based amorphous alloy thin strip. In the concavoconvex part, the height difference HL between the highest point (equivalent to the highest point in the thickness direction of the thin strip, equivalent to the uppermost part in the figure) and the lowest point (equivalent to the lowest point in the thickness direction of the thin strip, equivalent to the lowermost part in the figure) is measured from the profile as above. It should be noted that for the height difference HL, the average value is obtained by measuring 3 points in each linear laser irradiation mark.
[0342] Tables 1 to 6 show the results of the height difference HL and the height difference HL×width WA.
[0343] Microscopic photographs of the linear laser irradiation marks on the laser irradiated surface A of No. 54 shown in Tables 1 to 6 are shown in FIG. Fig.13 A microscope photograph of a linear laser irradiation mark on the back side B of the laser irradiated surface A is shown in Fig.14 . Fig.13 , 14 , the width WA and the width WB of the linear laser irradiation mark are shown respectively. In the Fe-based amorphous alloy thin strip No. 54, a linear laser irradiation mark is formed on the laser-irradiated surface A. Furthermore, a linear laser irradiation mark is also formed on the back surface B of the laser-irradiated surface A. In addition, no stress wrinkles are observed at the edge of the linear laser irradiation mark on the back surface B of the laser-irradiated surface A.
[0344] In addition, a microscopic photograph of a linear laser irradiation mark on the laser irradiated surface A of No. *44 shown in Tables 1 to 6 is shown in FIG. Fig.15 A microscope photograph of a linear laser irradiation mark on the back side B of the laser irradiated surface A is shown in Fig.16 . Fig.15 , 16 In the figure, the width WA and the width WB of the linear laser irradiation mark are shown respectively. In the Fe-based amorphous alloy thin strip No.*44, a linear laser irradiation mark is formed on the laser-irradiated surface A. The linear laser irradiation mark on the laser-irradiated surface A has slight ripples in the linear direction, which shows that the laser is too strong. In addition, a linear laser irradiation mark is also formed on the back side B of the laser-irradiated surface A. A stress wrinkle 1 is formed at the edge of the linear laser irradiation mark on the back side B of the laser-irradiated surface A.
[0345] In addition, microscopic photographs of linear laser irradiation marks on the laser-irradiated surface A of each of No. 13, 17, 20, and 24 in Tables 1 to 6 are shown in FIG. Fig.17 Microscopic photographs of linear laser irradiation marks on the laser-irradiated surface A of each of No. 26, 28, 34, and 36 are shown in Fig.18 No.13 is Fig.17 A, No.17 is Fig.17 B, No.20 is Fig.17 C, No.24 is Fig.17 D, No.26 is Fig.18 A, No.28 is Fig.18 B, No.34 is Fig.18 C, No.36 is Fig.18 D. Although other embodiments have been observed, they are all similar to Fig.17 , 18 It should be noted that the microscope photos were taken at a magnification of 1000 times. Fig.17 , 18As shown, the linear laser irradiation marks of the embodiment are linear (extending in the lateral direction in the figure).
[0346] [Comparative Example 1]
[0347] The same operation as in Example 1 was performed except that the laser processing was not performed.
[0348] The results are shown in No.*1 of Tables 1 to 6.
[0349] [Table 1]
[0350]
[0351] Note 1: No. with * is a comparative example
[0352] [Table 2]
[0353]
[0354] Note 1: No. with * is a comparative example
[0355] [Table 3]
[0356]
[0357] Note 1: No. with * is a comparative example
[0358] [Table 4]
[0359]
[0360] Note 1: No. with * is a comparative example
[0361] [Table 5]
[0362]
[0363] Note 1: No. with * is a comparative example
[0364] [Table 6]
[0365]
[0366] Note 1: No. with * is a comparative example
[0367] The relationship between the height difference HL×width WA and the iron loss CL (60 Hz, 1.45 T) of each sample shown in Tables 1 to 4 is shown in FIG. Figure 4 As shown in Tables 1 to 4 and Figure 4 As shown, the height difference HL×width WA is 6.0 to 180 μm 2 When the Fe-based amorphous alloy thin strip with low iron loss can be obtained, specifically, at this time, the iron loss CL (60 Hz, 1.45 T) of 0.15 W / kg or less can be obtained.
[0368] In addition, as shown in Tables 1 to 4, when the width WA is 28 μm or more and the height difference HL×width WA is 6.0 to 180 μm, 2 When the Fe-based amorphous alloy thin strip with low iron loss can be obtained, specifically, at this time, the iron loss CL (60 Hz, 1.45 T) of 0.15 W / kg or less can be obtained.
[0369] In addition, as shown in Tables 1 to 4, when the height difference HL is 0.20 or more and the height difference HL×width WA is 6.0 to 180 μm, 2 When the Fe-based amorphous alloy thin strip with low iron loss can be obtained.
[0370] Specifically, at this time, a core loss CL (60 Hz, 1.45 T) of 0.15 W / kg or less can be obtained.
[0371] The relationship between the height difference HL×width WA and the excitation power VA (60 Hz, 1.45 T) of each sample shown in Tables 1 to 4 is shown in FIG. Figure 6 As shown in Tables 1 to 4 and Figure 6 As shown in the figure, if the value of height difference HL×width WA increases, there is a tendency for the excitation power VA to increase. However, if the value of height difference HL×width WA is 180μm 2 Below, it is possible to suppress a significant increase in the exciting power VA.
[0372] The relationship between the height difference HL×width WA and the coercive force Hc (60 Hz, 1.45 T) of each sample shown in Tables 1 to 4 is shown in Figure 7 As shown in Tables 1 to 4 and Figure 7 As shown, the height difference HL×width WA is 6.0 to 180 μm 2 When , the coercive force can be reduced.
[0373] In addition, as shown in Tables 5 and 6, when there is no stress wrinkle at the edge of the linear laser irradiation mark on the back surface B of the laser irradiated surface A, a Fe-based amorphous alloy thin strip with low iron loss can be obtained. Specifically, at this time, an iron loss CL (60 Hz, 1.45 T) of 0.15 W / kg or less can be obtained.
[0374] The absence of the stress wrinkles is a result of confirmation using a microscope photograph taken at a magnification of 1000 times.
[0375] also, Fig. 22 The relationship between the width ratio WB / WA and the iron loss (60 Hz, 1.45 T) shown in Tables 5 and 6 is shown. Here, No. *1 is excluded. Fig. 22As shown in Tables 5 and 6, it can be seen that if the width ratio WB / WA of the width WB of the linear laser irradiation mark on the back surface B of the laser irradiated surface A to the width WA of the linear laser irradiation mark on the laser irradiated surface A is 0.57 or less (including 0), a Fe-based amorphous alloy thin strip with low iron loss can be obtained. Specifically, at this time, an iron loss CL (60 Hz, 1.45 T) of 0.15 W / kg or less can be obtained.
[0376] The relationship between the width WA and the iron loss CL (60 Hz, 1.45 T) of each sample shown in Tables 1 to 4 is shown in Figure 5 As shown in Tables 1 to 4 and Figure 5 As shown in Tables 5 and 6, when only the width WA of the linear laser irradiation mark on the laser-irradiated surface A is concerned, if the width WA is 28.5 μm or more and 90 μm or less, a low-loss Fe-based amorphous alloy thin strip can be obtained. In addition, when the width ratio WB / WA of the width WB of the linear laser irradiation mark on the back surface B of the laser-irradiated surface A to the width WA is 0.57 or less (including 0), a low-iron-loss Fe-based amorphous alloy thin strip can be obtained. Specifically, at this time, an iron loss CL (60 Hz, 1.45 T) of less than 0.15 W / kg can be obtained.
[0377] In addition, as shown in Tables 1 to 4 and Figure 5 As shown, even if the width WA is 28.26μm, even if the width WA is 121.30μm, if the height difference HL×width WA is a predetermined value, a Fe-based amorphous alloy thin strip with low iron loss can be obtained. Specifically, at this time, an iron loss CL (60Hz, 1.45T) of less than 0.15W / kg can be obtained. That is, if the height difference HL×width WA is a predetermined value, a Fe-based amorphous alloy thin strip with low iron loss can be obtained when the width WA is 28μm or more.
[0378] The relationship between the width WA and the excitation power VA (60 Hz, 1.45 T) of each sample shown in Tables 1 to 4 is shown in Fig.19 As shown in Tables 1 to 4 and Fig.19 As shown in FIG. 1 , if the value of the width WA increases, there is a tendency for the excitation power VA to increase. However, if the width WA is 90.0 μm or less, a significant increase in the excitation power VA can be suppressed. It should be noted that if the height difference HL×width WA is a predetermined value, a significant increase in the excitation power VA can be suppressed even if the width WA is 121.30 μm.
[0379] The relationship between the width WA and the coercive force Hc (60 Hz, 1.45 T) of each sample shown in Tables 1 to 4 is shown in Fig. 20 As shown in Tables 1 to 4 and Fig. 20As shown, when only the width WA is concerned, the coercive force can be reduced when the width WA is 28.5 to 90.0 μm. It should be noted that if the height difference HL×width WA is a predetermined value, the coercive force can be reduced even when the width WA is 121.30 μm.
[0380] In addition, the relationship between the line spacing LP1 and the iron loss CL (60 Hz, 1.45 T) of the examples (excluding the comparative examples) shown in Tables 1 to 4 is shown in FIG. Fig.21 According to Tables 1 to 4 and Fig.21 When the line spacing is 2 mm or more and 60 mm or less, the iron loss CL (60 Hz, 1.45 T) becomes less than 0.150 W / kg, and a Fe-based amorphous alloy thin strip with low loss at 60 Hz and 1.45 T can be obtained. Fig.21 Even if the line spacing LP1 is lengthened, there is no tendency for the iron loss to increase sharply. It is believed that even if the line spacing is greater than 60 mm and reaches 80 mm, 100 mm, and 200 mm, it is possible to obtain Fe-based amorphous alloy thin strips with low iron loss CL (60 Hz, 1.45 T).
[0381] <Characteristics before heat treatment>
[0382] The properties before heat treatment were evaluated using the samples shown in Tables 1 to 4. The results are shown in Table 7. The numbers (No) in Table 7 correspond to the Nos in Tables 1 to 4. The properties were evaluated based on values obtained from a DC BH curve measured at a maximum applied magnetic field of 800 A / m.
[0383] The coercive force Hc of the Fe-based amorphous alloy thin strip disclosed in the present invention before heat treatment is 5.0 A / m or less. In addition, regarding the rectangular ratio at this time, although No. 48 is 41.5%, other embodiments disclosed in the present invention have obtained a rectangular ratio of 40% or less. By laser irradiation, even for the thin strip before heat treatment, the effect of subdividing the magnetic domain can be obtained, and it becomes a state that is easy to magnetize.
[0384] [Table 7]
[0385]
[0386] Note 1: No. with * is a comparative example
[0387] <Characteristics at 1kHz frequency and 1T magnetic flux density>
[0388] Using the sample of Example 1, the iron loss CL and the exciting power VA were evaluated under the conditions of a frequency of 1 kHz and a magnetic flux density of 1 T. The results are shown in Table 8. It should be noted that No. in Table 8 corresponds to No. in Tables 1 to 4.
[0389] The relationship between the height difference HL and the iron loss CL (1kHz, 1T) at this time is shown in Fig.23 According to Table 8 and Fig.23 The Fe-based amorphous alloy thin strip disclosed in the present invention can obtain an iron loss of 8.6 W / kg or less under the conditions of a frequency of 1 kHz and a magnetic flux density of 1 T. It can be seen that by forming the linear laser irradiation marks disclosed in the present invention, the iron loss at high frequencies can be reduced. In addition, there is a tendency that the greater the height difference, the lower the iron loss (1 kHz, 1 T).
[0390] In addition, the relationship between the high-low difference HL and the excitation power VA (1kHz, 1T) is shown in Fig.24 According to Table 8 and Fig.24 The Fe-based amorphous alloy ribbon disclosed in the present invention can obtain an excitation power of 8.7VA / kg or less under the conditions of a frequency of 1kHz and a magnetic flux density of 1T. It can be seen that by forming the linear laser irradiation marks disclosed in the present invention, the excitation power at high frequencies can be reduced. In addition, there is a tendency that the greater the height difference, the lower the excitation power (1kHz, 1T).
[0391] Next, the relationship between the height difference HL×width WA and the iron loss CL (1kHz, 1T) is shown in Fig.25 .
[0392] According to Table 8 and Fig.25 The Fe-based amorphous alloy thin strip disclosed in the present invention can obtain an iron loss of 8.6 W / kg or less under the conditions of frequency 1 kHz and magnetic flux density 1 T. It can be seen that by forming the linear laser irradiation marks disclosed in the present invention, the iron loss at high frequency can be reduced. In addition, there is a tendency that the larger the height difference HL×width WA, the lower the iron loss CL (1 kHz, 1 T).
[0393] In addition, the relationship between the height difference HL×width WA and the excitation power VA (1kHz, 1T) is shown in Fig.26 According to Table 8 and Fig.26 The Fe-based amorphous alloy thin strip disclosed in the present invention can obtain an excitation power of less than 8.7VA / kg under the conditions of frequency 1kHz and magnetic flux density 1T. It can be seen that by forming the linear laser irradiation marks disclosed in the present invention, the excitation power under high frequency can be reduced.
[0394] Next, the relationship between laser density and iron loss CL (1kHz, 1T) is shown in Fig. 27 According to Table 8 and Fig. 27 The Fe-based amorphous alloy ribbon disclosed in the present invention can obtain an iron loss of 8.6 W / kg or less under the conditions of a frequency of 1 kHz and a magnetic flux density of 1 T. It can be seen that by forming the linear laser irradiation marks disclosed in the present invention, the iron loss at high frequencies can be reduced. In addition, there is a tendency that the greater the laser density, the lower the iron loss CL (1 kHz, 1 T).
[0395] In addition, the relationship between laser density and excitation power VA (1kHz, 1T) is shown in Fig.28 According to Table 8 and Fig.28 The Fe-based amorphous alloy thin strip disclosed in the present invention can obtain an excitation power of less than 8.7VA / kg under the conditions of frequency 1kHz and magnetic flux density 1T. It can be seen that by forming the linear laser irradiation marks disclosed in the present invention, the excitation power under high frequency can be reduced.
[0396] As can be seen from the above, the Fe-based amorphous alloy thin strip disclosed in the present invention is also useful for high-frequency applications.
[0397] [Table 8]
[0398]
[0399] The relationship between the laser density and the iron loss CL (60 Hz, 1.45 T) of each sample shown in Tables 1 to 4 is shown in Fig.29 According to Tables 1 to 4 and Fig.29 When the laser density is above 5 J / m and below 35 J / m, the iron loss CL (60 Hz, 1.45 T) becomes below 0.150 W / kg, and a Fe-based amorphous alloy thin strip with low loss at 60 Hz and 1.45 T can be obtained.
[0400] Next, the relationship between the laser density and the excitation power VA (60 Hz, 1.45 T) of each sample shown in Tables 1 to 4 is shown in FIG. Fig.30 According to Tables 1 to 4 and Fig.30 It can be seen that if the laser density is greater than 35 J / m, the excitation power VA increases sharply. Therefore, by setting the laser density to 35 J / m or less, the significant increase in the excitation power VA can be suppressed. In addition, when the laser density is 31 J / m or less, the increase in the excitation power VA is further suppressed.
[0401] In addition, the relationship between the laser density and the coercive force Hc (60 Hz, 1.45 T) of each sample shown in Tables 1 to 4 is shown in FIG. Fig.31 According to Tables 1 to 4 and Fig.31 It is known that if the laser density is greater than 35 J / m, the coercive force Hc increases sharply. Therefore, by setting the laser density to 35 J / m or less, the coercive force Hc can be reduced. In addition, when the laser density is 5 J / m to 35 J / m, a coercive force Hc of 3.0 A / m or less can be obtained.
[0402] [Example 2]
[0403] <Forming linear laser irradiation marks on the roller surface>
[0404] Using the same raw material thin strip as that used in Example 1, a linear laser irradiation mark was formed on the roll surface of the raw material thin strip under the conditions of a line interval LP1 of 20 mm, a scanning speed of 5 m / sec, and a laser density of 10 J / m. An observation photograph of the linear laser irradiation mark is shown in FIG. Fig.32 It should be noted that the heat treatment conditions are the same as those in Example 1.
[0405] The height difference HL of Example 2 is 1.04 μm, the width WA is 38.56 μm, and the height difference HL×width WA is 40.10 μm. 2 . In addition, the iron loss CL, excitation power VA, and coercive force Hc under the conditions of frequency 60 Hz and magnetic flux density 1.45 T are 0.0979 W / kg, 0.2413 VA / kg, and 2.0868 A / m, respectively, and the shape of the linear laser irradiation marks and the obtained characteristics are the same as those of the Fe-based amorphous alloy thin strip formed on the free solidification surface in Example 1. Therefore, it can be seen that the linear laser irradiation marks formed on either the free solidification surface or the roller surface can obtain substantially the same characteristics.
[0406] [Example 3]
[0407] The Fe-based amorphous alloy thin strip (chemical composition: Fe 82 4B 14 , thickness: 25μm, width: 142mm), a linear laser irradiation mark was formed under the conditions of a line interval LP1 of 20mm, a scanning speed of 8m / sec, and a laser density of 17J / m to form a Fe-based amorphous alloy thin strip sheet. The state of the linear laser irradiation mark is shown in Table 9. In Example 3, the width WA is 70.5μm and the width WB is 0μm. In addition, regarding the concave-convex state of the linear laser irradiation mark on the laser-irradiated surface A, the height difference HL is 0.44μm, and the height difference HL×width WA is 31.02μm 2 In addition, no linear laser irradiation marks were observed on the back side B of the laser irradiated surface A, and no stress wrinkles were observed.
[0408] A plurality of the obtained thin strip sheets are stacked to form a stacked body, and the stacked body is bent into a U-shape, and the two ends thereof are then wound around each other to form a Figure 8 and Fig. 9 The shape of the core is as shown in the figure. Figure 8 and Fig. 9 As shown, the window frame height A is 163 mm, the window frame width B is 72 mm, the belt body stacking thickness C is 25.3 mm, and the height D is 142 mm. In addition, the core has an area ratio of 88% and a weight of 13 kg.
[0409] It should be noted that the core Figure 8In addition, when a plurality of thin strips are stacked to form a laminate, a resin coating r is applied to the stacking surface of the middle abdomen of the laminate to prevent the thin strips from being separated from each other.
[0410] The iron loss CL and the exciting power VA of the obtained iron core were measured.
[0411] like Fig.10 As shown, a primary winding (N1) and a secondary winding (N2) are wound around the core as coils, the frequency is set to 60 Hz, and the magnetic flux density is set to 1.45 T and 1.5 T. In addition, the number of turns of the primary winding is 10 turns, and the number of turns of the secondary winding is 2 turns. In this way, a variable voltage circuit is made.
[0412] The voltage E (V) read by the power meter and the maximum magnetic flux density Bm (T) were converted and the excitation power (VA / kg) and iron loss (W / kg) at the specified magnetic flux density Bm (T) were calculated using the following equations 1, 2, and 3. The measurement results are shown in Table 10.
[0413] [Comparative Example 2]
[0414] Furthermore, as Comparative Example 2, similar measurements and evaluations were performed on an iron core produced in the same manner as above except that a thin ribbon piece on which no linear laser irradiation marks were formed was used.
[0415] Formula 1: Voltage E (V) = 4.443LF·C·W·N1·f·Bm×10 -6
[0416] Formula 2: Excitation power (VA / kg) = E·I / M
[0417] Formula 3: Iron loss (W / kg) = Watt / M
[0418] It should be noted that the details of the symbols in Formula 1 to Formula 3 are as follows.
[0419] E: Effective voltage measured by the power meter (V)
[0420] LF: Floor space ratio (=0.88)
[0421] C: Core stack thickness (mm)
[0422] W: Nominal width of the belt (mm)
[0423] N1: Number of windings of the excitation coil
[0424] f: Measurement frequency (Hz)
[0425] Bm: Maximum magnetic flux density or specified magnetic flux density
[0426] I: Effective current measured by the power meter (A)
[0427] M: Core weight (kg)
[0428] Watt: Power measured by a power meter (W)
[0429] [Table 9]
[0430]
[0431] [Table 10]
[0432]
[0433] As shown in Tables 9 and 10, the iron loss CL measured at 1.45T and 60Hz is 0.284W / kg in the case of an iron core using a thin strip sheet without linear laser irradiation marks. In contrast, the iron loss CL measured at 1.45T and 60Hz is 0.284W / kg in the case of an iron core using a thin strip sheet with linear laser irradiation marks according to the present embodiment is 0.197W / kg, which is a value reduced by about 30%.
[0434] It has never been possible to reduce the iron loss CL to 0.240 W / kg or less for the iron core. Therefore, by providing the coil in the iron core of this embodiment, a transformer with extremely low power loss can be obtained.
[0435] In addition, the iron loss CL measured at 1.50T and 60Hz is 0.310W / kg in the case of an iron core using a thin strip sheet without linear laser irradiation marks, while in contrast, it is 0.220W / kg in the case of an iron core using a thin strip sheet with linear laser irradiation marks according to the present embodiment, which is a value reduced by about 30%.
[0436] Using the iron core of Example 3 and the iron core of Comparative Example 2, the iron loss was evaluated by changing the magnetic flux density at a frequency of 50 Hz and 60 Hz. The results are shown in Table 11. In addition, the relationship between the magnetic flux density and the iron loss at a frequency of 50 Hz is shown in Fig.11 The relationship between the magnetic flux density and iron loss at a frequency of 60 Hz is shown in Fig.12 .
[0437] As shown in Table 11, Fig.11 , Fig.12 As shown, with the core of this embodiment, even if the magnetic flux density is changed at a frequency of 50 Hz and 60 Hz, a core with extremely low iron loss can be obtained.
[0438] [Table 11]
[0439]
[0440] <Example 4>
[0441] Fig.33 An example of the structure of the core and winding of the transformer of the present embodiment is shown in Table 12. The transformer comprises a toroidal core 21 formed by bending and winding a plurality of stacked Fe-based amorphous alloy ribbons, and a winding 22 wound around the core. The core of the first embodiment is composed of one toroidal core (single-phase two-leg wound core). The main characteristics and weight of a single-phase 50 Hz, 10 kVA rated capacity oil-immersed transformer (hereinafter, Example 4) using the core of this embodiment and in accordance with the present disclosure of JIS C 4304:2013 are shown in Table 12 by comparison with the prior art example 1. Here, the Fe-based amorphous alloy ribbon used in Example 4 has the above-mentioned characteristics, and is therefore marked as 25AMP06-88 according to the definition of "5 Symbols of types of amorphous ribbons" of JIS C 2534:2017. The Fe-based amorphous alloy ribbon used in the prior art example 1 is 25AMP08-88. It should be noted that the characteristics of the following Examples 4 to 11 are numerical values obtained through analysis based on simulations.
[0442] The Fe-based amorphous alloy strip used in Example 4 has a thickness of 25 μm and a width of 142.2 mm. The difference HL between the highest and lowest points of the linear laser irradiation mark formed on the free solidification surface is 0.62 μm. The iron loss at a frequency of 50 Hz and a magnetic flux density of 1.45 T is 0.075 W / kg, and the iron loss at a frequency of 60 Hz and a magnetic flux density of 1.45 T is 0.095 W / kg.
[0443] In addition, the Fe-based amorphous alloy thin strip used in Example 1 was 25 μm thick and 142.2 mm wide, with no laser irradiation marks formed. The iron loss at a frequency of 50 Hz and a magnetic flux density of 1.45 T was 0.130 W / kg, and the iron loss at a frequency of 60 Hz and a magnetic flux density of 1.45 T was 0.167 W / kg.
[0444] In the above-mentioned Example 4 and Conventional Example 1, the number of stacked layers of the winding-shaped iron core 21 is 1875 sheets, and Table 12 shows the weight thereof.
[0445] The primary winding of the transformer uses a copper wire with a diameter of 0.9 mm and is wound with 3143 turns. The secondary winding uses an aluminum flat wire of 3.2 mm × 6.0 mm, and a winding of 100 turns is connected in parallel.
[0446] [Table 12]
[0447]
[0448] According to Table 12, the no-load loss per unit weight of the core in Example 4 is 0.149 W / kg, which is about 25% lower than the no-load loss per unit weight of the core in Conventional Example 1 of 0.197 W / kg.
[0449] In addition, correspondingly, it can be seen that the ratio of the conventional example 1 to the energy efficiency standard value defined by JIS C 4304: 2013 is 0.73 (recorded as the "energy efficiency ratio" in Table 12. The same applies hereinafter.), while the example 4 can be improved to 0.70, and the annual CO2 emissions when the average equivalent load rate of the distribution transformer is 15% are also improved by about 17%. This can be understood based on the fact that the "annual CO2 emissions ratio when the load rate is 15%" recorded in Table 12 becomes 0.83 (the same applies hereinafter).
[0450] <Example 5>
[0451] As Fig.33 The second embodiment of the transformer having the core and winding structure of the present embodiment shown, shows the main characteristics and weight of the single-phase 60 Hz, rated capacity 10 kVA oil-immersed transformer (hereinafter, embodiment 5) of the present disclosure in accordance with JIS C 4304:2013 in comparison with the conventional example 2 in Table 13.
[0452] The Fe-based amorphous alloy thin strip used in Example 5 is the same as that in Example 4, and the Fe-based amorphous alloy thin strip used in Conventional Example 2 is the same as that in Conventional Example 1.
[0453] In the above-mentioned Example 5 and Conventional Example 2, the number of stacked layers of the coil-shaped iron core 21 is 1785, and Table 13 shows the weight thereof.
[0454] The primary winding of the transformer uses a copper wire with a diameter of 0.9 mm and is wound with 2776 turns. The secondary winding uses an aluminum flat wire of 2.6 mm × 6.0 mm, and a winding of 88 turns is connected in parallel.
[0455] [Table 13]
[0456]
[0457] According to Table 13, the no-load loss per unit weight of the core in Example 5 is 0.180 W / kg, which is about 30% lower than the no-load loss per unit weight of the core in Conventional Example 2, which is 0.259 W / kg.
[0458] In addition, correspondingly, it can be seen that the ratio of the energy efficiency standard value defined by JIS C 4304:2013 is 0.72 in the previous example 2, but it can be improved to 0.67 in the embodiment 5, and the annual CO2 emissions when the average equivalent load factor of the distribution transformer is 15% are also improved by about 20%.
[0459] <Example 6>
[0460] As Fig.33 The third embodiment of the transformer having the core and winding structure of the present embodiment shown, the main characteristics and weight of the single-phase 50 Hz, rated capacity 30 kVA oil-immersed transformer (hereinafter, embodiment 6) disclosed in accordance with JIS C 4304:2013 are shown in Table 14 by comparison with the previous example 3.
[0461] The Fe-based amorphous alloy strip used in Example 6 has a thickness of 25 μm and a width of 213.4 mm. The difference HL between the highest and lowest points of the linear laser irradiation mark formed on the free solidification surface is 0.52 μm. The iron loss at a frequency of 50 Hz and a magnetic flux density of 1.45 T is 0.076 W / kg, and the iron loss at a frequency of 60 Hz and a magnetic flux density of 1.45 T is 0.097 W / kg.
[0462] In addition, the Fe-based amorphous alloy thin strip used in Example 3 was 25 μm thick and 213.4 mm wide, with no laser irradiation marks formed. The iron loss at a frequency of 50 Hz and a magnetic flux density of 1.45 T was 0.132 W / kg, and the iron loss at a frequency of 60 Hz and a magnetic flux density of 1.45 T was 0.168 W / kg.
[0463] In the above-mentioned Example 6 and Conventional Example 3, the number of stacked layers of the winding-shaped iron core 21 is 3015 sheets, and Table 14 shows the weight thereof.
[0464] The primary winding of the transformer uses a copper wire with a diameter of 1.4 mm and is wound with 1509 turns. The secondary winding uses an aluminum flat wire of 3.2 mm × 15 mm, and a winding of 44 turns is connected in parallel.
[0465] [Table 14]
[0466]
[0467] According to Table 14, the no-load loss per unit weight of the core in Example 6 is 0.126 W / kg, which is about 36% lower than the no-load loss per unit weight of the core in Conventional Example 3, which is 0.197 W / kg.
[0468] In addition, correspondingly, it can be seen that the ratio of the energy efficiency standard value defined by JIS C 4304:2013 is 0.72 in the previous example 3, but it can be improved to 0.67 in the example 6, and the annual CO2 emission when the average equivalent load rate of the distribution transformer is 15% is also improved by about 22%. In addition, the no-load loss per unit weight of the core of the example 4 is 0.149W / kg, while it is 0.126W / kg in the example 6, which is an improvement of 0.023W / kg. The reason is that due to the enlargement of the core, the ratio of the length of the curved portion of the core to the magnetic path length becomes smaller, which suppresses the no-load loss caused by the residual stress of the curved portion of the core.
[0469] <Example 7>
[0470] As Fig.33 The fourth embodiment of the transformer having the core and winding structure of the present embodiment shown, shows the main characteristics and weight of the single-phase 60 Hz, rated capacity 30 kVA oil-immersed transformer (hereinafter, embodiment 7) disclosed in accordance with JIS C 4304:2013 in comparison with the previous example 4 in Table 15.
[0471] The Fe-based amorphous alloy thin strip used in Example 7 is the same as that in Example 6, and the Fe-based amorphous alloy thin strip used in Conventional Example 4 is the same as that in Conventional Example 3.
[0472] In the above-mentioned Example 7 and Conventional Example 4, the number of stacked layers of the winding-shaped iron core 21 is 2715 sheets, and Table 15 shows the weight thereof.
[0473] The primary winding of the transformer uses a copper wire with a diameter of 1.3 mm and is wound with 1509 turns. The secondary winding uses an aluminum flat wire of 4.0 mm × 13 mm, and a winding of 44 turns is connected in parallel.
[0474] [Table 15]
[0475]
[0476] According to Table 15, the no-load loss per unit weight of the core in Example 7 is 0.161 W / kg, which is about 37% lower than the no-load loss per unit weight of the core in Example 4, which is 0.256 W / kg.
[0477] In addition, correspondingly, it can be seen that the ratio of the energy efficiency standard value defined by JIS C 4304:2013 is 0.72 in the conventional example 4, but it can be improved to 0.66 in the embodiment 7, and the annual CO2 emission when the average equivalent load rate of the distribution transformer is 15% is also improved by about 24%. In addition, the no-load loss per unit weight of the core of the embodiment 5 is 0.180W / kg, while it is 0.161W / kg in the embodiment 7, which is an improvement of 0.019W / kg. This is reduced for the reasons explained in the embodiment 6.
[0478] <Example 8>
[0479] Fig.34 Another example of the configuration of the core and winding of the transformer of the present embodiment is shown in FIG. The transformer comprises: a 3-phase 3-leg wound core (a combination of 3 winding cores) obtained by combining a winding core 21 formed by bending and winding a plurality of stacked Fe-based amorphous alloy thin strips, and 3 sets of windings 22 wound around the core. The main characteristics and weight of a 3-phase 50 Hz, 100 kVA rated capacity oil-immersed transformer (hereinafter, Example 8) using the core of the embodiment and in accordance with the present disclosure of JIS C 4304:2013 are shown in Table 16 by comparison with the conventional example 5.
[0480] The Fe-based amorphous alloy thin strip used in Example 8 is the same as that in Example 6, and the Fe-based amorphous alloy thin strip used in Conventional Example 5 is the same as that in Conventional Example 3.
[0481] In the above-mentioned Example 8 and Conventional Example 5, the number of stacked layers of the coil-shaped iron cores 21 is 3480, and Table 16 shows the weight (the total weight of the three coil-shaped iron cores).
[0482] The primary winding of the above-mentioned embodiment 8 uses a copper wire with a diameter of 2.2 mm and is wound in a star connection with 653 turns, and the secondary winding uses a flat wire of 0.4 mm×247 mm made of aluminum and is connected in a delta connection to form a winding of 36 turns. In addition, the primary winding of the conventional example 5 uses a copper wire with a diameter of 2.2 mm and is wound in a star connection with 653 turns, and the secondary winding uses a flat wire of 0.4 mm×248 mm made of aluminum and is connected in a delta connection to form a winding of 36 turns.
[0483] [Table 16]
[0484]
[0485] According to Table 16, the no-load loss per unit weight of the core in Example 8 is 0.188 W / kg, which is about 30% lower than the no-load loss per unit weight of the core in Conventional Example 5, which is 0.269 W / kg.
[0486] In addition, correspondingly, it can be seen that the ratio of the energy efficiency standard value defined by JIS C 4304:2013 is 0.78 in the previous example 5, but it can be improved to 0.72 in the embodiment 8, and the annual CO2 emissions when the average equivalent load factor of the distribution transformer is 15% are also improved by about 21%.
[0487] <Example 9>
[0488] As Fig.34 Another embodiment of the transformer having the core and winding structure of the present embodiment shown is a 3-phase 60 Hz, 100 kVA rated capacity oil-immersed transformer (hereinafter, Example 9) disclosed in accordance with JIS C 4304:2013, and its main characteristics and weight are shown in Table 17 by comparison with the conventional Example 6.
[0489] The Fe-based amorphous alloy thin strip used in Example 9 is the same as that in Example 6, and the Fe-based amorphous alloy thin strip used in Conventional Example 6 is the same as that in Conventional Example 3. In the above-mentioned Example 9 and Conventional Example 6, the number of stacked layers of the winding core 21 is 2895 sheets, and the weight thereof is shown in Table 17.
[0490] The primary winding and secondary winding of the transformer are set to be the same as those in Example 8 and Conventional Example 5.
[0491] [Table 17]
[0492]
[0493] According to Table 17, the no-load loss per unit weight of the core in Example 9 is 0.238 W / kg, which is about 30% lower than the no-load loss per unit weight of the core in Example 6, which is 0.339 W / kg.
[0494] In addition, correspondingly, it can be seen that the ratio of the energy efficiency standard value defined by JIS C 4304:2013 is 0.81 in the previous example 6, but it can be improved to 0.76 in the embodiment 9, and the annual CO2 emissions when the average equivalent load factor of the distribution transformer is 15% are also improved by about 21%.
[0495] <Example 10>
[0496] As Fig.34 Another embodiment of the transformer having the core and winding structure of the present embodiment shown is a 3-phase 50 Hz, 500 kVA rated capacity oil-immersed transformer (hereinafter, Example 10) disclosed in accordance with JIS C 4304:2013, and its main characteristics and weight are shown in Table 18 by comparison with the prior art example 7.
[0497] The Fe-based amorphous alloy thin strip used in Example 10 is the same as that in Example 6, and the Fe-based amorphous alloy thin strip used in Conventional Example 7 is the same as that in Conventional Example 3.
[0498] In the above-mentioned Example 10 and Conventional Example 7, regarding the spiral core 21, the number of stacked layers is 5685 in Example 10 and 5955 in Conventional Example 7. Table 18 shows their weight (total of three spiral cores).
[0499] The primary winding of the above-mentioned embodiment 10 uses a 3.5mm×4.5mm flat copper wire, which is wound in a star connection for 399 turns, and the secondary winding uses an aluminum 1.3mm×438mm flat wire, which is connected in a delta connection to form a winding of 22 turns. In addition, the primary winding of the conventional example 7 uses a 3.2mm×5.0mm flat copper wire, which is wound in a star connection for 381 turns, and the secondary winding uses an aluminum 1.4mm×383mm flat wire, which is connected in a delta connection to form a winding of 21 turns.
[0500] [Table 18]
[0501]
[0502] According to Table 18, the no-load loss per unit weight of the core in Example 10 is 0.163 W / kg, which is about 34% lower than the no-load loss per unit weight of the core in Example 7, which is 0.246 W / kg.
[0503] In addition, correspondingly, it can be seen that the ratio of the energy efficiency standard value defined by JIS C 4304:2013 is 0.93 in the previous example 7, but it can be improved to 0.90 in the example 10, and the annual CO2 emission when the average equivalent load rate of the distribution transformer is 15% is also improved by about 18%. In addition, the no-load loss per unit weight of the core of the example 8 is 0.188W / kg, while it is 0.163W / kg in the example 10, which is an improvement of 0.025W / kg. The reason is that due to the enlargement of the core, the ratio of the length of the curved portion of the core to the magnetic path length becomes smaller, which suppresses the no-load loss caused by the residual stress of the curved portion of the core.
[0504] <Example 11>
[0505] Fig.35 2 shows another example of the configuration of the core and windings of the transformer of this embodiment. The transformer comprises: a 3-phase 5-leg wound core obtained by combining a plurality of stacked Fe-based amorphous alloy thin strips into a ring-shaped core 21, and 3 sets of windings 22 wound around the core.
[0506] Table 19 shows main characteristics and weight of a 3-phase 50 Hz, 1000 kVA rated capacity oil-immersed transformer (hereinafter, Example 11) of the present disclosure using the core of this embodiment and in compliance with JIS C 4304:2013, in comparison with Conventional Example 8.
[0507] The Fe-based amorphous alloy thin strip used in Example 11 is the same as that in Example 6, and the Fe-based amorphous alloy thin strip used in Conventional Example 8 is the same as that in Conventional Example 3.
[0508] In the above-mentioned embodiment 11 and the prior art example 8, the encircling iron core 21 is a stack of 2610 iron cores. Fig.35 It is obtained by overlapping two in the vertical direction, and its weight (total of 8 surrounding iron cores) is shown in Table 19.
[0509] The primary winding of the above-mentioned embodiment 11 uses a 2.8mm×7.0mm flat copper wire, which is wound with 377 turns in a delta connection, and the secondary winding uses an aluminum 3.0mm×305mm flat wire, which is wound with 12 turns in a delta connection. In addition, the primary winding of the conventional example 8 uses a 2.8mm×7.0mm flat copper wire, which is wound with 377 turns in a delta connection, and the secondary winding uses an aluminum 3.2mm×306mm flat wire, which is wound with 12 turns in a delta connection.
[0510] [Table 19]
[0511]
[0512] According to Table 19, the no-load loss per unit weight of the core in Example 11 is 0.179 W / kg, which is about 33% lower than the no-load loss per unit weight of the core in Conventional Example 8, which is 0.269 W / kg. In addition, correspondingly, it can be seen that the energy efficiency standard value defined by JIS C 4304:2013 is 1.00 in Conventional Example 8, but it can be improved to 0.99 in Example 11, and the annual CO2 emission when the average equivalent load rate of the distribution transformer is 15% is also improved by about 16%.
[0513] As described above, the transformer disclosed in the present invention can reduce no-load loss, and is therefore particularly effective in reducing loss and CO2 emissions in distribution transformers with low average equivalent load factors. It should be noted that in this embodiment, the application in a wound core transformer is described in detail, but it goes without saying that the effect of reducing no-load loss can also be achieved in the case of a stacked core transformer.
[0514] All documents, patent applications, and technical standards described in this specification are incorporated herein by reference to the same extent as if each individual document, patent application, or technical standard was specifically and individually indicated to be incorporated by reference.
Claims
1. An Fe-based amorphous alloy thin strip having a first surface and a second surface, At least the first surface has a plurality of continuous linear laser irradiation marks, The linear laser irradiation mark is a linear laser irradiation mark formed by a continuous wave CW oscillation method and arranged in a direction perpendicular to the casting direction of the Fe-based amorphous alloy thin strip. The surface of the linear laser irradiation mark has unevenness, and when the unevenness is evaluated in the casting direction, the height difference HL×width WA calculated from the height difference HL between the highest point and the lowest point in the thickness direction of the Fe-based amorphous alloy thin strip and the length of the linear laser irradiation mark in the casting direction in the first surface, that is, the width WA, is 6.0 to 180 μm 2 , The iron loss of the Fe-based amorphous alloy thin strip is less than 0.130 W / kg under the conditions of a frequency of 60 Hz and a magnetic flux density of 1.45 T. 2 . The Fe-based amorphous alloy ribbon according to claim 1 , wherein the width WA is greater than or equal to 28 μm. 3 . The Fe-based amorphous alloy thin strip according to claim 1 , wherein the height difference HL is greater than or equal to 0.20 μm.
4. The Fe-based amorphous alloy ribbon according to claim 1, wherein the linear laser irradiation mark is a molten solidified portion melted and solidified by irradiating the first surface with laser light, and extends from the first surface to the second surface. A width ratio WB / WA of a length of the linear laser irradiation mark in the second surface in the casting direction, that is, a width WB to the width WA is 0.57 or less. 5 . The Fe-based amorphous alloy ribbon according to claim 1 , wherein a length, that is, a width WA, of the linear laser irradiation mark on the first surface in the casting direction is not less than 28.5 μm and not more than 90 μm. 6 . The Fe-based amorphous alloy strip according to claim 1 , wherein, when a line interval is defined as a distance between adjacent linear laser irradiation marks among the plurality of linear laser irradiation marks, the line interval is 2 mm to 200 mm. 7 . The Fe-based amorphous alloy ribbon according to claim 1 , wherein the portion where the linear laser irradiation mark is provided is amorphous.
8. According to any one of claims 1 to 5, for the Fe-based amorphous alloy strip, when the direction perpendicular to the casting direction is set as the width direction, in the width direction, the proportion of the length of the linear laser irradiation mark in the total length of the Fe-based amorphous alloy strip is in the range of 10% to 50% in the direction from the center of the width direction of the Fe-based amorphous alloy strip toward the two ends of the width direction.
9. The Fe-based amorphous alloy thin strip according to any one of claims 1 to 5, which has a free solidification surface and a roll surface as the first surface and the second surface, The maximum cross-sectional height Rt of a portion other than the linear laser irradiation mark in the free solidification surface is 3.0 μm or less. 10 . The Fe-based amorphous alloy thin strip according to claim 1 , which has a thickness of 18 μm to 35 μm.
11. The Fe-based amorphous alloy strip according to any one of claims 1 to 5, wherein the alloy composition of the Fe-based amorphous alloy strip consists of Fe, Si, B and impurities, and when the total content of Fe, Si and B is set to 100 atomic %, the content of Fe is greater than 78 atomic %, the content of B is greater than 10 atomic %, and the total content of B and Si is 17 atomic % to 22 atomic %. 12 . The Fe-based amorphous alloy thin strip according to claim 1 , wherein the iron loss is 8.6 W / kg or less and the excitation power VA is 8.7 VA / kg or less under the conditions of a frequency of 1 kHz and a magnetic flux density of 1 T. 13 . The Fe-based amorphous alloy ribbon according to claim 1 , wherein a coercive force Hc of a DC BH curve measured at a maximum applied magnetic field of 800 A / m is 5.0 A / m or less.
14. The Fe-based amorphous alloy thin strip according to claim 13, wherein the squareness ratio of the DC BH curve measured at a maximum applied magnetic field of 800 A / m, that is, residual magnetic flux density Br / maximum magnetic flux density Bm, is 40% or less.
15. A method for manufacturing a Fe-based amorphous alloy thin strip, wherein: irradiating at least the first surface of an Fe-based amorphous alloy thin strip having a first surface and a second surface with a laser using a continuous wave (CW) oscillation method, thereby obtaining an Fe-based amorphous alloy thin strip having a plurality of linear laser irradiation marks, The laser density of the laser using the continuous wave CW oscillation method is 5 J / m or more and 35 J / m or less, The linear laser irradiation mark is arranged in a direction perpendicular to the casting direction of the Fe-based amorphous alloy thin strip, The surface of the linear laser irradiation mark has unevenness, and when the unevenness is evaluated in the casting direction, the height difference HL×width WA calculated from the height difference HL between the highest point and the lowest point in the thickness direction of the Fe-based amorphous alloy thin strip and the length of the linear laser irradiation mark in the casting direction in the first surface, that is, the width WA, is 6.0 to 180 μm 2 , The iron loss of the Fe-based amorphous alloy thin strip is less than 0.130 W / kg under the conditions of a frequency of 60 Hz and a magnetic flux density of 1.45 T.
16. The method for manufacturing an Fe-based amorphous alloy thin strip according to claim 15, wherein the linear laser irradiation mark extends from the first surface to the second surface. A width ratio WB / WA of a length (width WB) of the linear laser irradiation mark on the second surface in the casting direction to a length (width WA) of the linear laser irradiation mark on the first surface in the casting direction is 0.57 or less. 17 . The method for producing an Fe-based amorphous alloy thin strip according to claim 15 , wherein the length of the linear laser irradiation mark in the first surface in the casting direction, that is, the width WA, is 28 μm or more.
18. The method for manufacturing an Fe-based amorphous alloy strip according to claim 15 or 16, wherein the surface of the linear laser irradiation mark has projections and depressions, and when the projections and depressions are evaluated in the casting direction, the height difference HL between the highest point and the lowest point in the thickness direction of the Fe-based amorphous alloy strip is 0.20 to 2.0 μm. 19 . The method for producing an Fe-based amorphous alloy thin strip according to claim 15 , wherein the portion where the linear laser irradiation mark is provided is amorphous. 20 . The method for producing an Fe-based amorphous alloy thin strip according to claim 15 , wherein when the interval between adjacent linear laser irradiation marks among the plurality of linear laser irradiation marks is defined as a line interval, the line interval is 2 mm to 200 mm.
21. An iron core, which is formed by laminating a plurality of Fe-based amorphous alloy thin strips according to any one of claims 1 to 5, or by winding at least one Fe-based amorphous alloy thin strip according to any one of claims 1 to 5.
22. The iron core according to claim 21, which is formed by bending and winding a plurality of stacked Fe-based amorphous alloy thin strips. The iron loss at the frequency of 60Hz and the magnetic flux density of 1.45T is less than 0.240W / kg.
23. A transformer comprising: An iron core using the Fe-based amorphous alloy thin strip according to any one of claims 1 to 5, and a coil wound around the iron core.
24. The transformer according to claim 23, wherein the iron core is formed by bending and winding a plurality of stacked Fe-based amorphous alloy thin strips, and the iron loss under the conditions of a frequency of 60 Hz and a magnetic flux density of 1.45 T is less than 0.240 W / kg.
25. The transformer according to claim 23, which is a single-phase transformer, and the no-load loss per unit weight of the iron core at 50 Hz is less than 0.15 W / kg, or the no-load loss per unit weight of the iron core at 60 Hz is less than 0.19 W / kg.
26. The transformer according to claim 23, which is a three-phase transformer, wherein the no-load loss per unit weight of the iron core at 50 Hz is less than 0.19 W / kg, or the no-load loss per unit weight of the iron core at 60 Hz is less than 0.24 W / kg.
27. The transformer according to claim 23, having a rated capacity of 10 kVA or more.
